Air filter and method for manufacturing the same

The air filter with a nonwoven fabric coated with a fluorine-containing functional group and silica sol gel effectively captures and repels oil mist and dust, addressing clogging issues and ensuring easy regeneration, thus enhancing air purification efficiency.

CN115052673BActive Publication Date: 2024-12-20MITSUBISHI MATERIALS ELECTRONICS CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080095696.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-04
Filing Date
2020-12-17
Publication Date
2024-12-20
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Existing air filters for purifying air containing oil mist and dust face issues with clogging due to static electricity, poor oil repellency, and moisture blocking, leading to inefficient air purification and difficulty in removing captured oil mist.

Method used

An air filter with a nonwoven fabric coated with a water- and oil-repellent film containing a fluorine-containing functional group component and silica sol gel, which repels oil mist and dust, allowing air permeability of 1 ml/cm²/sec to 30 ml/cm²/sec, and facilitates easy removal of accumulated oil mist and dust.

Benefits of technology

The air filter effectively captures and repels oil mist and dust, preventing clogging and allowing easy regeneration by removing accumulated oil mist and dust, while maintaining high air permeability and reducing static electricity issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115052673B_ABST
    Figure CN115052673B_ABST
Patent Text Reader

Abstract

An air filter comprises a nonwoven fabric having a plurality of pores formed between fibers, the plurality of pores extending between one side through which air containing oil mist and dust flows in and another side opposite to the one side through which the air flows out. A water- and oil-repellent film is formed on the fiber surface of the nonwoven fabric. The water- and oil-repellent film comprises a fluorine-containing functional group component (A) and a silica sol gel (C), wherein the fluorine-containing functional group component (A) is contained at a ratio of 0.01% to 10% by mass when the silica sol gel (C) is 100% by mass, or the fluorine-containing functional group component (A) is contained at a ratio of 1% to 30% by mass when the water- and oil-repellent film is 100% by mass. The air permeability of the air filter is 1 ml / cm 2 / sec~30ml / cm 2 / sec, the fluorinated functional group component (A) contains a perfluoroether structure represented by the following formula (1). p F 2p+1 ‑O‑C q F 2q ‑O‑C r F 2r ‑X‑Y (1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an air filter for purifying air containing oil mist and dust and a method for manufacturing the same. More specifically, the present invention relates to an air filter having an oil-repellent film formed on the fiber surface of a nonwoven fabric and a method for manufacturing the same. Background Art

[0002] In machine tools such as cutting machines or turning machines that use cutting fluid to process metal products, the cutting fluid is scattered due to the high-speed operation of the machine, thereby generating oil mist and dust. These oil mist and dust deteriorate the working environment and reduce its working efficiency. Therefore, as an air filter that purifies air containing oil mist and dust, an air filter material has been proposed, which can not only suppress the clogging caused by dust floating in the air, but also suppress the clogging caused by oil mist (for example, claim 1 of patent document 1, paragraphs

[0006] ,

[0021] ,

[0045] , and

[0053] to

[0060] of the specification).

[0003] The air filter material comprises a first PTFE (polytetrafluoroethylene) porous membrane and a second PTFE porous membrane, and the airflow passes through the first PTFE porous membrane and the second PTFE porous membrane in the order of the first main surface of the air filter material to the second main surface of the air filter material. The thickness of the first PTFE porous membrane is in the range of 4 to 40 μm, and the specific surface area of ​​the first PTFE porous membrane is 0.5 m 2 / g or less, the specific surface area of ​​the second PTFE porous membrane is greater than the specific surface area of ​​the first PTFE porous membrane, and is within the range of 1.5 to 10 m 2 / g or less.

[0004] Regarding the first and second PTFE porous membranes, a mixture formed by adding PTFE powder and a liquid lubricant is formed into a sheet-like molded body. The first PTFE porous membrane is manufactured by the following method: the sheet-like molded body is heated and stretched in the longitudinal (MD) direction at a temperature above the melting point (327°C) of PTFE and at a ratio of 50 times or more, and then heated and stretched in the transverse (TD) direction at a temperature of 130 to 400°C to 5 to 8 times the length before stretching. The second PTFE porous membrane is manufactured by the following method: the sheet-like molded body of PTFE is heated and stretched in the MD direction at a temperature lower than the melting point of PTFE (270 to 290°C) and at a ratio of 15 to 40 times, and then further heated and stretched in the TD direction at a temperature of 120 to 130°C to 15 to 40 times the length before stretching, at the same ratio as when stretched in the MD direction.

[0005] Patent Document 1: Japanese Patent Publication No. 2018-51546

[0006] In the air filter material disclosed in Patent Document 1, the first PTFE porous membrane is manufactured by increasing the stretching temperature and the stretching ratio compared with the second PTFE porous membrane, thereby reducing the specific surface area of ​​the first PTFE porous membrane to 0.5 m 2 / g or less, thereby capturing large-diameter dust and oil mist. On the other hand, the specific surface area of ​​the second PTFE porous membrane is increased to 1.5 to 10 m 2 / g, thereby capturing small particle size dust and oil mist.

[0007] Yet, in the disclosed air filter material of patent documentation 1, even utilize the first and second PTFE porous membrane to trap the dust and the oil mist that particle diameter is different, also because the PTFE porous membrane easily produces static electricity, and is difficult to remove the static electricity that produces, therefore is not easy to be processed into filter shape.In addition, because water repellency is higher than oil repellency, therefore the moisture that is included in the atmosphere sometimes blocks the PTFE porous membrane, and dust easily adheres to this porous membrane.Therefore, if continue to use air filter material, then there is the problem that oil mist continues to remain in the inside of air filter material and easily blocks the air filter material. Summary of the invention

[0008] An object of the present invention is to provide an air filter that can purify air containing oil mist and dust and prevent clogging. Another object of the present invention is to provide a method for simply manufacturing an air filter that can purify air containing oil mist and dust and prevent clogging.

[0009] A first aspect of the present invention is an air filter comprising a nonwoven fabric having a plurality of pores formed between fibers, the plurality of pores extending between a side through which air containing oil mist and dust flows in and another side opposite to the side through which the air flows out, a water- and oil-repellent film being formed on the fiber surface of the nonwoven fabric, the water- and oil-repellent film comprising a fluorine-containing functional group component A and a silica sol gel C, the fluorine-containing functional group component A being contained at a ratio of 0.01% to 10% by mass when the silica sol gel C is set to 100% by mass (hereinafter, sometimes referred to as “in the silica sol gel C”), or the fluorine-containing functional group component A being contained at a ratio of 1% to 30% by mass when the water- and oil-repellent film is set to 100% by mass, and the air permeability of the air filter being 1 ml / cm 2 / sec~30ml / cm 2 / sec, the fluorine-containing functional group component A comprises a perfluoroether structure represented by the following formula (1) or (2).

[0010] C p F 2p+1-OC q F 2q -OC r F 2r -XY (1)

[0011] C p F 2p+1 -OC q F 2q -XY (2)

[0012] In the above formula (1) and the above formula (2), p, q and r are each the same or different integers of 1 to 6, and the perfluoroether structure may be linear or branched. In addition, in the above formula (1) and the above formula (2), X is a hydrocarbon group having 2 to 10 carbon atoms, and may contain one or more bonds selected from ether bonds, CO-NH bonds, O-CO-NH bonds and sulfonamide bonds. Furthermore, in the above formula (1) and the above formula (2), Y is a hydrolyzate of silane or a main component of a silica sol-gel.

[0013] The second viewpoint of the present invention is an invention based on the first viewpoint, wherein the water-repellent and oil-repellent film comprises oxide particles B with an average particle size of 2nm to 90nm bonded to the fluorine-containing functional group component A and a silica sol gel C, and when the water-repellent and oil-repellent film is set to 100 mass %, the fluorine-containing functional group component A and the oxide particles B are contained in a total ratio of 5 mass % to 80 mass %, and the mass ratio A / B of the fluorine-containing functional group component A to the oxide particles B is in the range of 0.05 to 0.80.

[0014] The third viewpoint of the present invention is an invention based on the first viewpoint, wherein the fluorine-containing functional group component A has a first fluorine-containing functional group component A1 bonded to oxide particles B with an average particle size of 2nm to 90nm and a second fluorine-containing functional group component A2 contained in the silica sol gel C, and when the water-repellent and oil-repellent film is set to 100% by mass, the total content ratio of the first fluorine-containing functional group component A1 and the second fluorine-containing functional group component A2 is 1% to 30% by mass, and the mass ratio C:B of the silica sol gel C to the oxide particles B is in the range of 10:90 to 90:10.

[0015] A fourth aspect of the present invention is the invention based on the second aspect or the third aspect, wherein the oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn, and Zr.

[0016] A fifth aspect of the present invention is the invention based on the third aspect, wherein the content ratio of the first fluorine-containing functional group component A1 is equal to or greater than the content ratio of the second fluorine-containing functional group component A2 in terms of mass ratio.

[0017] A sixth aspect of the present invention is the invention based on the first aspect, wherein the silica sol gel C further contains 0.5 to 20% by mass of an alkylene component having 2 to 7 carbon atoms, when the silica sol gel C is 100% by mass.

[0018] A seventh aspect of the present invention is the invention based on the first aspect, wherein the nonwoven fabric is composed of a single layer or a laminate of a plurality of layers.

[0019] The eighth aspect of the present invention is an invention based on the first aspect, wherein the fibers constituting the nonwoven fabric are one or more fibers selected from polyethylene terephthalate (PET), polypropylene (PP), glass, alumina, carbon, cellulose, pulp, nylon and metal.

[0020] The ninth aspect of the present invention is a method for manufacturing an air filter, comprising the following steps: adding a catalyst to a mixed solution of silicon alkoxide, a fluorine-based compound containing the fluorine-containing functional group component A of the first aspect, alcohol and water to prepare a liquid composition for forming a water-repellent and oil-repellent film; mixing the liquid composition for forming a water-repellent and oil-repellent film and a solvent to prepare a diluted solution; immersing a non-woven fabric in the diluted solution; and dehydrating and drying the immersed non-woven fabric to form a water-repellent and oil-repellent film on the fiber surface of the non-woven fabric.

[0021] The tenth aspect of the present invention is a method for manufacturing an air filter, comprising the following steps: dispersing the oxide particles B of the second aspect in an organic solvent to prepare a dispersion of the oxide particles; mixing a fluorine-containing compound containing the fluorine-containing functional group component A of the first aspect, water and a catalyst in the dispersion of the oxide particles to prepare a dispersion of fluorine-containing oxide particles; adding a catalyst to a mixed solution of silicon alkoxide, alcohol and water to prepare a silica sol-gel solution; mixing the dispersion of the fluorine-containing oxide particles and a diluted solution of the silica sol-gel solution to prepare a liquid composition for forming a water-repellent and oil-repellent film; immersing a non-woven fabric in the diluted solution of the liquid composition for forming a water-repellent and oil-repellent film; and dehydrating and drying the non-woven fabric after immersion.

[0022] According to an eleventh aspect of the present invention, the oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

[0023] The twelfth aspect of the present invention is a method for manufacturing an air filter, comprising the following steps: dispersing the oxide particles B of the third aspect in an organic solvent to prepare a dispersion of the oxide particles; mixing a fluorine-containing compound containing the first fluorine-containing functional group component A1 of the third aspect, water and a catalyst in the dispersion of the oxide particles to prepare a dispersion of fluorine-containing oxide particles; adding and mixing a catalyst into a mixed solution formed by mixing a fluorine-containing compound containing the second fluorine-containing functional group component A2 of the third aspect, a silicon alkoxide, an alcohol and water to prepare a fluorine-containing silica sol-gel solution; mixing the dispersion of the fluorine-containing oxide particles and the fluorine-containing silica sol-gel solution to prepare a liquid composition for forming a water-repellent and oil-repellent film; immersing a non-woven fabric in a diluted solution of the liquid composition for forming a water-repellent and oil-repellent film; and dehydrating and drying the non-woven fabric after immersion.

[0024] A thirteenth aspect of the present invention is the invention according to the twelfth aspect, wherein the oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

[0025] In the air filter of the first aspect of the present invention, a water-repellent and oil-repellent film is formed on the fiber surface of the nonwoven fabric, the water-repellent and oil-repellent film comprises a fluorine-containing functional group component A and a silica sol gel C, the fluorine-containing functional group component A is represented by the aforementioned formula (1) or formula (2) and has a water-repellent and oil-repellent function, when the silica sol gel C is set to 100 mass%, the fluorine-containing functional group component A is contained at a ratio of 0.01 mass% to 10 mass%, or when the water-repellent and oil-repellent film is set to 100 mass%, the fluorine-containing functional group component A is contained at a ratio of 1 mass% to 30 mass%, and the air permeability of the air filter is limited to 1 ml / cm 2 / sec~30ml / cm 2 Therefore, when the air containing oil mist and dust flows into the air filter from one side of the air filter, the oil mist and dust are captured by the non-woven fabric, and only the air passes through the pores of the non-woven fabric and flows out from the other side of the air filter, so that the air becomes clean.

[0026] At this time, due to the oil repellency of the fluorine-containing functional group component A of the water-repellent and oil-repellent film and the air permeability of the air filter being 1 ml / cm 2 / sec~30ml / cm 2 / second, so the oil mist will not be adsorbed by the water-repellent and oil-repellent film on the fiber surface of the non-woven fabric, but will only be repelled and attached. If the air filter is used continuously and the amount of oil mist captured inside the non-woven fabric increases, then when the air filter is horizontally arranged, the oil mist will gather on the other side of the air filter along with the air passing through in a liquefied form, and when the air filter is vertically arranged, the captured oil mist will gather at the lower end of the air filter due to its own weight and will not block the pores of the non-woven fabric. In this way, the pore blockage caused by the oil mist can be suppressed.

[0027] On the other hand, since the air permeability of the air filter is 1ml / cm 2 / sec~30ml / cm 2 / second, so the dust directly adheres to the water-repellent and oil-repellent film on the fiber surface of the non-woven fabric, or adheres to the oil mist attached to the water-repellent and oil-repellent film. Therefore, when the air filter is clogged with dust and the like after long-term use, if a pneumatic shaker or the like is used to impact the air filter, the dust attached together with the oil mist can be easily removed, thereby enabling air filter regeneration. Since the water-repellent and oil-repellent film contains silica sol gel C, the adhesion of the water-repellent and oil-repellent film to the non-woven fabric is improved.

[0028] In the air filter of the second aspect of the present invention, since the water-repellent and oil-repellent film includes oxide particles B bonded with fluorine-containing functional group component A, the oxide particles B can improve the water-repellent and oil-repellent function and can improve the film strength. In addition, the silica sol gel C improves the adhesion of the water-repellent and oil-repellent film to the nonwoven fabric.

[0029] In the air filter according to the third aspect of the present invention, since the first fluorinated functional group component A1 is bonded to the oxide particles B and the second fluorinated functional group component A2 is contained in the silica sol-gel C, the water- and oil-repellent function of the water- and oil-repellent film can be further improved.

[0030] In the air filter of the fourth aspect of the present invention, since the oxide particles contained in the water-repellent and oil-repellent film are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr, oxide particles suitable for the use environment of the air filter can be included from a variety of oxide particles.

[0031] In the air filter according to the fifth aspect of the present invention, since the mass ratio of the first fluorinated functional group component A1 to the second fluorinated functional group component A2 is the same or the first fluorinated functional group component A1 is contained in a larger amount than the second fluorinated functional group component A2, the water- and oil-repellent film has high adhesion to the fiber surface of the nonwoven fabric.

[0032] In the air filter of the sixth aspect of the present invention, since the silica sol gel C contains 0.5% to 20% by mass of alkylene components having 2 to 7 carbon atoms when the silica sol gel is set to 100% by mass, the water-repellent and oil-repellent film is well in contact with the fibers of the non-woven fabric, and the thickness of the water-repellent and oil-repellent film becomes uniform, which can give the water-repellent and oil-repellent film a better oil-repellent performance.

[0033] In the air filter of the seventh aspect of the present invention, when the nonwoven fabric is composed of a single layer, it becomes an air filter with a simple structure. When the nonwoven fabric is composed of a multi-layer stack, each layer can be constructed according to properties such as the particle size of the flowing dust and the size of the oil particles in the oil mist.

[0034] In the air filter of the eighth aspect of the present invention, the material of the fibers constituting the non-woven fabric can be selected from polyethylene terephthalate (PET), polypropylene (PP), polytetrafluoroethylene (PTFE), glass, alumina, carbon, cellulose, pulp, nylon and metal according to the properties such as the particle size of the dust flowing in, the size of the oil particles in the oil mist, or the content of the alkylene component with 2 to 7 carbon atoms formed by hydrolysis of epoxysilane in the liquid composition for forming the oil-repellent film described later.

[0035] In the manufacture method of the 9th viewpoint of the present invention, by adding catalyst in the mixed solution that silicon alkoxide, fluorine compound, alcohol and water are mixed to prepare water-repellent and oil-repellent film-forming liquid composition, in the diluent of the water-repellent and oil-repellent film-forming liquid composition, impregnate nonwoven fabric and make nonwoven fabric deliquescence and dry to manufacture air filter, therefore water-repellent and oil-repellent film can be uniformly formed on the fiber surface of nonwoven fabric.In addition, different from the PTFE porous membrane of patent documentation 1, in water-repellent and oil-repellent film, it is difficult to generate static electricity, and air filter can be manufactured simply.

[0036] In the manufacture method of the tenth viewpoint of the present invention, by mixing the dispersion liquid of fluorine oxide particles and silica sol gel liquid to prepare water-repellent and oil-repellent film-forming liquid composition, in the diluent of the water-repellent and oil-repellent film-forming liquid composition, impregnate nonwoven fabrics and make nonwoven fabrics deliquescence and dry, thereby manufacture air filter, therefore can form water-repellent and oil-repellent film uniformly on the fiber surface of nonwoven fabrics.In addition, owing to there being oxide particles that particle surface is water-repellent and oil-repellent in silica sol gel, therefore easily maintain the air permeability of nonwoven fabrics while reducing water-repellent and oil-repellent.In addition, different from the PTFE porous membrane of patent documentation 1, in water-repellent and oil-repellent film, it is difficult to produce static electricity, can manufacture air filter simply.

[0037] In the manufacturing method of the eleventh aspect of the present invention, since the oxide particles are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr, it is possible to manufacture an air filter that includes oxide particles suitable for the use environment of the air filter from a variety of oxide particles.

[0038] In the manufacture method of the 12th viewpoint of the present invention, because fluorine-containing oxide particles are present in the silica sol-gel comprising fluorine-based compounds, therefore when the liquid composition is impregnated into the fiber surface of nonwoven fabric and dried, water and oil repellency can be further given to the nonwoven fabric. In addition, the air permeability of the nonwoven fabric is easily reduced. In addition, different from the PTFE porous membrane of patent documentation 1, it is difficult to generate static electricity in water and oil repellent film, and air filter can be manufactured simply.

[0039] In the manufacturing method of the thirteenth aspect of the present invention, since the oxide particles are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr, it is possible to manufacture an air filter that includes oxide particles suitable for the use environment of the air filter from a variety of oxide particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a side view of a single-layer nonwoven fabric according to the first embodiment of the present invention.

[0041] Figure 2 This is a side view of the double-layer nonwoven fabric according to the first embodiment of the present invention.

[0042] Figure 3 This is a flow chart for manufacturing the air filter according to the first embodiment of the present invention.

[0043] Figure 4 It is a side view of a single-layer nonwoven fabric according to a second embodiment of the present invention.

[0044] Figure 5 This is a side view of a double-layer nonwoven fabric according to a second embodiment of the present invention.

[0045] Figure 6 This is a flow chart for manufacturing the air filter according to the second embodiment of the present invention.

[0046] Figure 7 It is a side view of a single-layer nonwoven fabric according to a third embodiment of the present invention.

[0047] Figure 8 This is a side view of a double-layer nonwoven fabric according to a third embodiment of the present invention.

[0048] Fig. 9 This is a flow chart for manufacturing the air filter according to the third embodiment of the present invention. DETAILED DESCRIPTION

[0049] Next, a mode for carrying out the present invention will be described with reference to the drawings.

[0050] <First Embodiment>

[0051] [Air filter]

[0052] like Figure 1 As shown in FIG. 1 , the air filter 10 of the first embodiment includes a nonwoven fabric 20 and a water-repellent and oil-repellent film 21 formed on the fiber surface of the nonwoven fabric. The nonwoven fabric 20, which is a main component of the air filter 10, has a side 20a into which air containing oil mist and dust flows and another side 20b opposite to the side 20a from which the air flows out, and the nonwoven fabric 20 is composed of a single layer. Figure 2 As shown, the air filter 50 may also be composed of a double-layer laminate of an upper nonwoven fabric 30 and a lower nonwoven fabric 40. In this case, the upper surface of the upper nonwoven fabric 30 becomes a side 30a into which the air containing oil mist and dust flows, and the lower surface of the lower nonwoven fabric 40 becomes the other side 40b opposite to the side 30a. In addition, the laminate is not limited to a double layer, and may also be composed of multiple layers such as three layers and four layers.

[0053] like Figure 1 As shown in the enlarged view of FIG. 1 , the nonwoven fabric 20 is formed by entanglement of a plurality of fibers 20c, and pores 20d are formed between the fibers. The pores 20d penetrate between one side 20a and the other side 20b of the nonwoven fabric 20. A water-repellent and oil-repellent film 21 is formed on the surface of the fibers 20c of the nonwoven fabric. The unit weight of the nonwoven fabric is preferably 200 g / m 2 ~400g / m 2 , but is not limited to this range. The water-repellent and oil-repellent film 21 is formed by a silica sol gel which is a silica sol hydrolyzate, and the silica sol gel contains a fluorine-containing functional group component having oil repellency as shown in the above formula (1) or formula (2). When the silica sol gel is set to 100% by mass, the fluorine-containing functional group component is contained at a ratio of 0.01% to 10% by mass. In the state of the air filter 10 having the water-repellent and oil-repellent film 21 formed on the fiber surface, the nonwoven fabric 20 is made to have a viscosity of 1 ml / cm 2 / sec~30ml / cm 2 The air permeability was measured using a Frazier-type tester described in JIS-L1913:2000.

[0054] If the unit area weight of the non-woven fabric is less than 200g / m 2 If the fiber pores are too large, the dust collection capacity will be insufficient. 2 , since the air permeability is less than 1ml / cm2 / second, dust can easily block the pores between fibers or the air permeability is too low, so the air filter is prone to pressure loss due to the resistance of the air sent into the air filter, and the efficiency of the air supply energy is prone to deterioration.

[0055] If the fluorine-containing functional group component is less than 0.01% by mass when the silica sol-gel forming the water-repellent and oil-repellent film is set to 100% by mass, the oil-repellent effect is lacking and the performance of repelling oil mist is insufficient. That is, when the oil mist reaches the air filter, the oil mist wets and spreads on the fiber surface, and easily blocks the pores 20d.

[0056] If the fluorine-containing functional group component exceeds 10% by mass, the adhesion of the water-repellent and oil-repellent film to the nonwoven fabric will deteriorate. The weight per unit area of ​​the nonwoven fabric is more preferably 220 g / m 2 ~350g / m 2 In addition, when the silica sol-gel is taken as 100 mass %, it is preferred that the fluorine-containing functional group component is contained in the range of 0.1 mass % to 5 mass %.

[0057] If the air permeability is less than 1ml / cm 2 / second, the ventilation is poor, and air containing oil mist and dust is difficult to pass through. If it exceeds 30ml / cm 2 / second, the size of the pores 20d of the nonwoven fabric is much larger than the particle sizes of the oil particles 22 and dust particles 23 in the oil mist flowing into the air, and the oil particles 22 and dust particles 23 pass through the pores of the nonwoven fabric together with the air and pass through the air filter 10, and the oil mist and dust cannot be captured. The air permeability is preferably 1.5ml / cm 2 / sec~25ml / cm 2 / Second.

[0058] The function of the air filter 10 will be described. Figure 1 As shown, the air containing oil mist and dust reaches one side 20a of the nonwoven fabric 20 constituting the air filter 10. Here, since the air filter 10 has a predetermined air permeability and since the water-repellent and oil-repellent film 21 exhibits oil repellency, the oil particles 22 of the oil mist cannot pass through the air filter 13 not only when the particle size is larger than the aperture size of the pore 20d, but also when the particle size is slightly smaller than the aperture size of the pore 20d, but are only repelled by the water-repellent and oil-repellent film 21 between the fibers 20c and 20c of the nonwoven fabric 20 and attached to the water-repellent and oil-repellent film 21. At the same time, the dust particles 23 are also only attached to the water-repellent and oil-repellent film 21. As a result, the oil mist and dust are captured by the nonwoven fabric 20, and only the air passes through the air filter 13 formed therein. Figure 1 The pores 20 d between the fibers 20 c shown in the enlarged view of FIG. 2 reach the other side 20 b , thereby passing through the nonwoven fabric 20 .

[0059] If the air filter is continued to be used and the amount of oil mist captured inside the nonwoven fabric is increased, then when the air filter is horizontally configured, the oil mist is accompanied by the air passing through in a liquefied form and gathered on the other side of the air filter, and when the air filter is vertically configured, the captured oil mist is gathered at the lower end of the air filter due to its own weight and will not block the pores of the nonwoven fabric. Thus, the pore blockage caused by the oil mist can be suppressed. Dust is directly attached to the water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric, or attached to the oil mist attached to the water-repellent and oil-repellent film. By regularly utilizing a pneumatic shaker or the like to impact the air filter 10, the oil mist and dust accumulated in the nonwoven fabric 20 can be removed from the air filter 10.

[0060] [Manufacturing method of air filter]

[0061] The air filter is generally manufactured by the following method.

[0062] like Figure 3 As shown, a liquid composition for forming a water-repellent and oil-repellent film is prepared by mixing silicon alkoxide, alcohol, a fluorine-containing functional group component A and water, and mixing an alkylene component as needed, and adding a catalyst to the mixed solution. A diluent is prepared by mixing a solvent in the liquid composition for forming a water-repellent and oil-repellent film, impregnating a nonwoven fabric 20 in the diluent and pulling it from the diluent, spreading the nonwoven fabric on a horizontal metal mesh or the like in the atmosphere at room temperature, deliquating until a certain amount of liquid is reached and drying, thereby forming a water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric, and then heat-treating the nonwoven fabric in the atmosphere at a temperature of 30°C to 120°C for 1 hour to 24 hours, thereby manufacturing an air filter 10.

[0063] [Preparation of nonwoven fabric]

[0064] First, prepare a 1.1 ml / cm 2 / sec~40ml / cm 2 Specifically, in a state where a water-repellent and oil-repellent film described later is formed on the fiber surface of the nonwoven fabric, a nonwoven fabric having an air permeability of 1 ml / cm 2 / sec~30ml / cm 2 When the water-repellent and oil-repellent film is formed of a plurality of thick films, a nonwoven fabric with high air permeability is selected, and when the water-repellent and oil-repellent film is formed of a few thin films, a nonwoven fabric with low air permeability is selected.

[0065] As the nonwoven fabric, for example, there are cellulose mixed ester membrane filters, glass fiber filter paper, and nonwoven fabrics made by mixing polyethylene terephthalate fibers and glass fibers (produced by Anji Filter Paper Co., Ltd., trade name: 340). In this way, the nonwoven fabric is made of one or more fibers selected from polyethylene terephthalate (PET), polypropylene (PP), polytetrafluoroethylene (PTFE), glass, alumina, carbon, cellulose, pulp, nylon and metal. The fiber can also be a fiber mixed with two or more fibers. In order to obtain the above-mentioned air permeability, the thickness of the fiber (fiber diameter) is preferably 0.01μm to 10μm. Regarding the thickness of the nonwoven fabric, when the air filter is a single layer, it is preferably 0.2mm to 0.8mm, and when the air filter is a multi-layer laminate, the thickness of the laminate is preferably 0.2mm to 1.6mm. Since the main component of the water-repellent and oil-repellent film-forming material of the present invention is silica sol gel, in order to obtain close contact with the fiber, a material with hydroxyl groups is preferred. Among them, glass, alumina, cellulose nanofibers, etc. also have fine fiber diameters and can make the air permeability a low value within the above range.

[0066] As mentioned above, in the case of nonwoven fabrics, Figure 2 In the case of a laminated body formed by stacking a plurality of nonwoven fabrics 30, 40 as shown, by making the fibers of the nonwoven fabric 30 on the side into which the air containing oil mist and dust flows in glass fibers, the water-repellent and oil-repellent film containing silica sol gel as a main component is more firmly bonded to the glass fibers and is difficult to peel off from the fibers of the nonwoven fabric.

[0067] [Method for forming a water- and oil-repellent film on the fiber surface of a nonwoven fabric]

[0068] In order to form a water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric of the first embodiment, a liquid composition for forming a water-repellent and oil-repellent film described later is prepared by diluting the alcohol having a boiling point of less than 120°C and a carbon number in the range of 1 to 4 in a manner such that the mass ratio (liquid composition: alcohol) relative to the liquid composition reaches 1:1 to 50. The nonwoven fabric is immersed in the diluted liquid and pulled out from the diluted liquid. The nonwoven fabric is spread on a horizontal metal mesh or the like in the air at room temperature and dehydrated until a certain amount of liquid is reached. As another method, the pulled out nonwoven fabric is dehydrated by passing it through a squeeze roller (press). The dehydrated nonwoven fabric is dried in the air at a temperature of 25°C to 140°C for 0.5 to 24 hours. Thus, as Figure 1 As shown in the enlarged view of FIG. 2 , a water-repellent and oil-repellent film 21 is formed on the surface of the fiber 20c constituting the nonwoven fabric 20. When the amount of liquid removal is small, a thick film is formed on the fiber surface of the nonwoven fabric, and when the amount of liquid removal is large, a thin film is formed on the fiber surface of the nonwoven fabric.

[0069] [Method for producing a water- and oil-repellent film-forming liquid composition]

[0070] The liquid composition for forming a water- and oil-repellent film is produced by the following method.

[0071] [Preparation of mixed solution]

[0072] First, a mixed solution is prepared by mixing tetramethoxysilane or tetraethoxysilane as a silicon alkoxide, an epoxy-containing silane that becomes an alkylene component, a fluorine-containing silane that becomes a fluorine-containing functional group component, an alcohol having a boiling point lower than 120°C and a carbon number in the range of 1 to 4, and water. As the silicon alkoxide, specifically, tetramethoxysilane, its oligomer or tetraethoxysilane, its oligomer can be cited. For example, in order to obtain a highly durable water- and oil-repellent film, tetramethoxysilane is preferably used. On the other hand, in the case of avoiding methanol generated during hydrolysis, tetraethoxysilane is preferably used. The epoxy-containing silane that becomes the alkylene component is mixed as needed.

[0073] As the epoxy-containing silane that becomes the above-mentioned alkylene component, specifically, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane or multifunctional epoxysilane can be cited. Relative to the total mass of silicon alkoxide and alkylene component, 1% to 40% by mass of alkylene component is included, preferably 2.5% to 20% by mass of alkylene component is included. If the alkylene component is less than the lower limit of 1% by mass, when a film is formed on the fiber of a non-woven fabric that does not contain hydroxyl groups, the adhesion to the fiber is insufficient. In addition, if the upper limit of 40% by mass is exceeded, the durability of the formed film is reduced. If epoxy-containing silane is included in such a manner that the alkylene component is within the above-mentioned range of 1 to 40% by mass, the epoxy group also opens during the hydrolysis polymerization process and contributes to the polymerization, thereby improving the leveling property during the drying process and making the film thickness uniform. In addition, in the case where the fibers of the non-woven fabric contain hydrophilic groups such as glass fibers, the content of the alkylene component can be extremely small or zero. On the other hand, in the case where the fibers of the non-woven fabric do not contain hydrophilic groups, it is preferred to contain 0.5% to 20% by mass of the alkylene component when the silica sol gel is set to 100% by mass.

[0074] As for the alcohol having a carbon number in the range of 1 to 4, one or more alcohols in the range can be cited. As the alcohol, for example, methanol (boiling point 64.7°C), ethanol (boiling point about 78.3°C), propanol (n-propanol (boiling point 97-98°C), isopropanol (boiling point 82.4°C)) can be cited. Methanol or ethanol is particularly preferred. This is because these alcohols are easily mixed with silicon alkoxides. As the above-mentioned water, in order to prevent the mixing of impurities, it is best to use ion exchange water or pure water. A mixed solution is prepared by adding an alcohol having a carbon number in the range of 1 to 4 and water to silicon alkoxides and epoxy-containing silanes, and preferably stirring at a temperature of 10 to 30°C for 5 to 20 minutes.

[0075] [Preparation of water- and oil-repellent film-forming liquid composition]

[0076] The prepared mixed solution is mixed with a catalyst consisting of an organic acid, an inorganic acid or a titanium compound. At this time, the liquid temperature is preferably maintained at a temperature of 30°C to 80°C, preferably stirred for 1 hour to 24 hours. Thus, a water-repellent and oil-repellent film-forming liquid composition is prepared, the water-repellent and oil-repellent film-forming liquid composition comprising silicon alkoxide, epoxy silane that becomes an alkylene component, and fluorine-containing silane that becomes a fluorine-containing functional group component. By when water-repellent and oil-repellent film-forming liquid composition is set to 100 mass %, with silicon alkoxide as 2 mass %~50 mass %, epoxy silane as 30 mass % at most, fluorine-containing silane as fluorine-containing functional group component is 0.005 mass %~3 mass %, carbon number is 20 mass %~98 mass % in the range of 1~4 alcohol, water is 0.1 mass %~40 mass %, organic acid, inorganic acid or titanium compound as catalyst is 0.01 mass %~5 mass % ratio mixing, carry out silicon alkoxide, epoxy silane and hydrolysis reaction of fluorine-containing silane as fluorine-containing functional group component, thus obtain water-repellent and oil-repellent film-forming liquid composition.If the fluorine-containing silane as fluorine-containing functional group component is less than lower limit 0.005 mass %, then formed film is difficult to produce oil repellency, if it exceeds upper limit 3 mass %, then it is difficult to be in close contact with the fiber surface of nonwoven fabric.

[0077] The reason for limiting the ratio of alcohols having a carbon number of 1 to 4 to the above range is that if the ratio of alcohols is less than the lower limit, the silicon alkoxide will not dissolve in the solution but will separate, and the reaction solution will easily gel in the hydrolysis reaction. On the other hand, if it exceeds the upper limit, the amount of water and catalyst required for hydrolysis will be relatively reduced, so the reactivity of hydrolysis will decrease, polymerization will not progress, and the adhesion of the film will decrease. The reason for limiting the ratio of water to the above range is that if it is less than the lower limit, the polymerization will not progress due to the slow hydrolysis rate, and the adhesion of the water-repellent and oil-repellent film will be insufficient. On the other hand, if it exceeds the upper limit, the reaction solution will gel in the hydrolysis reaction, and there will be too much water, so the silicon alkoxide compound will not dissolve in the alcohol aqueous solution but will separate.

[0078] When the silica sol-gel is set to 100 mass %, the SiO2 concentration (SiO2 amount) is preferably 1 to 40 mass %. If the SiO2 concentration is less than the lower limit, the polymerization is insufficient, which easily causes a decrease in the adhesion of the film or the generation of cracks. If it exceeds the upper limit, the ratio of water becomes relatively high, resulting in the undesirable situation that the silicon alkoxide does not dissolve and the reaction solution gels.

[0079] Organic acid, inorganic acid or titanium compound functions as a catalyst for promoting the hydrolysis reaction. As an organic acid, formic acid and oxalic acid can be exemplified, as an inorganic acid, hydrochloric acid, nitric acid, phosphoric acid can be exemplified, as a titanium compound, tetrapropoxy titanium, tetrabutoxy titanium, tetraisopropoxy titanium, titanium lactate, etc. can be exemplified. The catalyst is not limited to the above substances. The reason for limiting the ratio of the above catalyst to the above range is that if it is less than the lower limit, polymerization is insufficient due to lack of reactivity, so no film is formed. On the other hand, even if the upper limit is exceeded, the reactivity will not be affected, but the residual acid will cause fiber corrosion of the non-woven fabric and other unfavorable conditions.

[0080] The fluorine-containing silane serving as the fluorine-containing functional group component is represented by the following formula (3) and formula (4). More specifically, the perfluoroether group in the above formula (3) and formula (4) includes perfluoroether structures represented by the following formulas (5) to (13).

[0081]

[0082] C2F5-O-C2F4-O-C2F4- (5)

[0083] C2F5-O-C3F6-O-C2F4- (6)

[0084] C3F7-O-C3F6-O-C2F4- (7)

[0085] C4F9-O-C3F6-O-C2F4- (8)

[0086] C3F7-O-C2F4-O-C2F4- (9)

[0087] C2F5-O-C2F4- (10)

[0088] C2F5-O-C3F6- (11)

[0089] C3F7-O-C3F6- (12)

[0090] C3F7-O-C4F8- (13)

[0091] In addition, as X in the above formula (2) and formula (3), structures represented by the following formulas (14) to (18) can be cited. In addition, the following formula (14) shows an example containing an ether bond, the following formula (15) shows an example containing an ester bond, the following formula (16) shows an example containing an amide bond, the following formula (17) shows an example containing a urethane bond, and the following formula (18) includes an example containing a sulfonamide bond.

[0092]

[0093] In the above formulas (14) to (18), R 2 and R 3 is a hydrocarbon group having 0 to 10 carbon atoms, R 4 is a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. 3 Examples of hydrocarbon groups include alkylene groups such as methylene and ethylene. 4 Examples of the hydrocarbon group include phenyl and the like in addition to alkyl groups such as methyl and ethyl.

[0094] In the above formula (3) and formula (4), R 1 Examples thereof include methyl, ethyl, and propyl.

[0095] In the above formula (3) and formula (4), Z is not particularly limited as long as it is a hydrolyzable group that can form a Si-O-Si bond by hydrolysis. As such a hydrolyzable group, specifically, for example, alkoxy groups such as methoxy, ethoxy, propoxy, butoxy, aryloxy groups such as phenoxy, naphthoxy, aralkyloxy groups such as benzyloxy, phenethoxy, acetoxy, propionyloxy, butyryloxy, valeryloxy, pivaloyloxy, benzoyloxy, etc. can be cited. Among them, methoxy and ethoxy are preferably used.

[0096] Here, as specific examples of fluorine-containing silanes that become fluorine-containing functional group components having perfluoroether structures represented by the above formulae (3) and (4), structures represented by the following formulae (19) to (27) can be cited. In the following formulae (19) to (27), R is a methyl group or an ethyl group.

[0097]

[0098] C3F7-O-C3F6-CH2-O-C3H6-Si-(OR)3 (23)

[0099]

[0100] As described above, the fluorine-containing functional group component contained in the liquid composition for forming a water-repellent and oil-repellent film of the first embodiment has a structure having one or more perfluoroether groups and one or more alkoxysilyl groups in the molecule, respectively, and has a perfluoroether group having a plurality of short-chain perfluoroalkyl and perfluoroalkylene groups having a carbon number of 6 or less bonded to an oxygen atom, and has a high fluorine content in the molecule, so that the formed film can be given excellent water-repellent and oil-repellent properties.

[0101] [Water- and oil-repellent film-forming liquid composition]

[0102] The first embodiment of the water- and oil-repellent film-forming liquid composition is manufactured by the above-mentioned manufacturing method, and comprises the aforementioned silica sol hydrolyzate containing a fluorine-containing functional group component and a solvent. The fluorine-containing functional group component has a perfluoroether structure represented by the above formula (1) and formula (2), and contains 0.01% to 10% by mass of the fluorine-containing functional group component when the silica sol gel is set to 100% by mass.

[0103] The solvent is a mixed solvent of water and an alcohol having 1 to 4 carbon atoms, or a mixed solvent of water, an alcohol having 1 to 4 carbon atoms and an organic solvent other than the alcohol. Specific examples of the perfluoroether structure include the structures represented by the above formulae (5) to (27).

[0104] Since the liquid composition for forming a water-repellent and oil-repellent film of the first embodiment contains silica sol-gel as a main component, a water-repellent and oil-repellent film having excellent adhesion to the fibers of a nonwoven fabric and a high-strength water-repellent and oil-repellent film that is difficult to peel off can be obtained. In addition, since the silica sol-gel contains a fluorinated functional group component of a perfluoroether structure shown in the above formula (1) or (2), it has an oil-repellent effect. If the content ratio of the fluorinated functional group component is less than 0.01% by mass, it is impossible to impart oil repellency to the formed film. If it exceeds 10% by mass, the film-forming property is poor due to the occurrence of film rejection, etc. The content ratio of the fluorinated functional group component is preferably 0.1% by mass to 5% by mass.

[0105] <Second Embodiment>

[0106] [Air filter]

[0107] like Figure 4 As shown, the air filter 110 of the second embodiment includes a nonwoven fabric 120 and a water-repellent and oil-repellent film 121 formed on the fiber surface of the nonwoven fabric. The nonwoven fabric 120, which is a main component of the air filter 110, has a side 120a into which air containing oil mist and dust flows and another side 120b opposite to the side 120a from which the air flows out, and the nonwoven fabric 120 is composed of a single layer. Figure 5 As shown, the air filter 150 may also be composed of a double-layer laminate of an upper nonwoven fabric 130 and a lower nonwoven fabric 140. In this case, the upper surface of the upper nonwoven fabric 130 becomes a side 130a into which the air containing oil mist and dust flows, and the lower surface of the lower nonwoven fabric 140 becomes the other side 140b opposite to the side 130a. In addition, the laminate is not limited to a double layer, and may also be composed of multiple layers such as three layers and four layers.

[0108] like Figure 4 As shown in the enlarged view of the center of the nonwoven fabric 120, the nonwoven fabric 120 is formed by entanglement of a plurality of fibers 120c, and pores 120d are formed between the fibers. The pores 120d penetrate between one side 120a and the other side 120b of the nonwoven fabric 120. A water-repellent and oil-repellent film 121 is formed on the surface of the fibers 120c of the nonwoven fabric. The unit weight of the nonwoven fabric is preferably 200 g / m 2 ~400g / m 2 , but is not limited to this range. The water-repellent and oil-repellent film 121 comprises oxide particles B having an average particle size of 2 nm to 90 nm and silica sol gel C. The oxide particles B are bonded with a fluorine-containing functional group component A represented by the above-mentioned formula (1) or formula (2). When the water-repellent and oil-repellent film 121 is set to 100 mass %, the fluorine-containing functional group component A is contained at a ratio of 1 mass % to 30 mass %. In addition, when the water-repellent and oil-repellent film 121 is set to 100 mass %, the fluorine-containing functional group component A and the oxide particles B are contained at a total ratio of 5 mass % to 80 mass %. In addition, the mass ratio A / B of the fluorine-containing functional group component A to the oxide particles B is in the range of 0.05 to 0.80.

[0109] like Figure 4As shown in the further enlarged view of the upper part of the water-repellent and oil-repellent film 121, a plurality of oxide particles 121a whose particle surfaces are covered with fluorine-containing functional group components are bonded by using silica sol-gel 121b as an adhesive. Since the water-repellent and oil-repellent film 121 includes oxide particles 121a, a thick film is formed in appearance, which can narrow the pores 120d between fibers. In addition, the film thickness can be controlled by changing the particle size of the oxide particles and the content ratio of the oxide particles in the film components.

[0110] If the unit area weight of the non-woven fabric is less than 200g / m 2 If the fiber pores are too large, the dust collection capacity will be insufficient. 2 , since the air permeability is less than 1ml / cm 2 / second, dust is easy to immediately block the pores between fibers or the air permeability is too low, so the air filter is prone to pressure loss due to the resistance of air sent into the air filter, and the efficiency of air supply energy is easy to deteriorate. The unit area weight of nonwoven fabric is more preferably 200g / m 2 ~350g / m 2 within the range.

[0111] In the state of the air filter 110 with the water-repellent and oil-repellent film 121 formed on the fiber surface, the nonwoven fabric 120 is manufactured to have a 1 ml / cm 2 / sec~30ml / cm 2 / second air permeability. If the air permeability is less than 1ml / cm 2 / second, the ventilation is poor, and air containing oil mist and dust is difficult to pass through. If it exceeds 30ml / cm 2 / second, the size of the pores 120d of the nonwoven fabric is much larger than the particle sizes of the oil particles 122 and dust particles 123 in the oil mist flowing into the air, and the oil particles 122 and dust particles 123 pass through the pores of the nonwoven fabric together with the air and pass through the air filter 110, and the oil mist and dust cannot be captured. The air permeability is preferably 1.5ml / cm 2 / sec~25ml / cm 2 / sec. The air permeability was measured using a Frazier-type tester described in JIS-L1913:2000.

[0112] If the water-repellent and oil-repellent film 121 is set to 100% by mass, the content ratio of the fluorine-containing functional group component A is less than 1% by mass, then the oil-repellent effect is lacking, and the performance of repelling oil mist is insufficient. That is, when the oil mist reaches the air filter, the oil mist wets and expands on the fiber surface, and it is easy to block the pores 120d. If the content ratio of the fluorine-containing functional group component A exceeds 30% by mass, the adhesion of the water-repellent and oil-repellent film to the nonwoven fabric deteriorates. When the water-repellent and oil-repellent film 121 is set to 100% by mass, the content ratio of the fluorine-containing functional group component A is preferably 5% to 25% by mass.

[0113] The average particle size of the oxide particles B contained in the water-repellent and oil-repellent film 121 is 2nm to 90nm, preferably in the range of 2nm to 85nm. If the average particle size is less than 2nm, it is easy to cause the aggregation of the oxide particles and it is difficult to disperse in the medium. If it exceeds 90nm, the oxide particles B fall off from the water-repellent and oil-repellent film. When the water-repellent and oil-repellent film 121 is set to 100% by mass, the total of fluorine-containing functional group components A and oxide particles B is contained at a ratio of 5% to 80% by mass, preferably 7% to 75% by mass, and the mass ratio A / B of fluorine-containing functional group components A and oxide particles B is 0.05 to 0.80, preferably in the range of 0.07 to 0.70. If the total of fluorine-containing functional group components A and oxide particles B is less than 5% by mass when the water-repellent and oil-repellent film 121 is set to 100% by mass, the oil repellency of the water-repellent and oil-repellent film is reduced. In addition, if the total exceeds 80% by mass, the content of silica sol gel C is relatively reduced, and the water-repellent and oil-repellent film will not be firmly bonded to the nonwoven surface. In addition, if the mass ratio A / B is less than 0.05, the oil repellency of the water-repellent and oil-repellent film is poor, and if it exceeds 0.80, the adhesion of the water-repellent and oil-repellent film to the fiber surface is reduced. In addition, in this specification, the average particle size of the oxide particles refers to the average value obtained by measuring the particle size of 200 points by image analysis in the particle shape observed by a transmission electron microscope (TEM).

[0114] This air filter 110 plays the same role as the air filter described in the first embodiment. Figure 4As shown, the air containing oil mist and dust reaches one side 120a of the nonwoven fabric 120 constituting the air filter 110. Here, since the air filter 110 has a predetermined air permeability and the water-repellent and oil-repellent film 121 exhibits oil repellency, the oil particles 122 of the oil mist cannot pass through the air filter 110 even when the particle size is larger than the pore size of the pore 120d, and even when the particle size is slightly smaller than the pore size of the pore 120d, but only adhere to the water-repellent and oil-repellent film 121 while being repelled by the water-repellent and oil-repellent film 121 between the fibers 120c and 120c of the nonwoven fabric 120. At the same time, the dust particles 123 also only adhere to the water-repellent and oil-repellent film 121. Since the water-repellent and oil-repellent film 121 contains oxide particles 121a, the film becomes uneven, and the oil particles 122 have a low degree of adhesion to the film, while the dust particles 123 are easily attached. Thus, the oil particles 122 of the oil mist and the dust particles 123 are captured by the nonwoven fabric, and the air containing the oil mist and the dust passes through the air gap formed in the Figure 4 As shown in the enlarged view, the pores 120d between the fibers 120c reach the other side 120b, become air without oil mist and dust, and pass through the non-woven fabric 120.

[0115] If the air filter is continued to be used and the amount of oil mist captured inside the nonwoven fabric is increased, then when the air filter is horizontally configured, the oil mist with a low degree of attachment to the film is accompanied by the air passing through in a liquefied form and gathered on the other side of the air filter, and when the air filter is vertically configured, the captured oil mist is gathered at the lower end of the air filter due to its own weight and will not block the pores of the nonwoven fabric. Thus, the pore blockage caused by the oil mist can be suppressed. Dust is directly attached to the water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric, or is attached to the oil mist attached to the water-repellent and oil-repellent film. By regularly utilizing a pneumatic shaker, etc., the air filter 110 is impacted, so that the oil mist and dust accumulated in the nonwoven fabric 120 can be removed from the air filter 110.

[0116] [Manufacturing method of air filter]

[0117] The air filter is generally manufactured by the following method.

[0118] like Figure 6 As shown, a dispersion of oxide particles is prepared by mixing oxide particles and an organic solvent. A fluorine-containing functional group component A is mixed in the dispersion, and water and a catalyst are further mixed to prepare a dispersion of fluorine-containing oxide particles. On the other hand, a silica sol-gel solution is prepared by mixing silicon alkoxide, alcohol and water and, if necessary, an alkylene component, and adding a catalyst to the mixed solution.

[0119] A liquid composition for forming a water-repellent and oil-repellent film is prepared by mixing a solvent in the silica sol-gel solution and mixing the mixed solution with the dispersion of the fluorine oxide particles. A diluent is prepared by diluting the liquid composition with a solvent, and a nonwoven fabric 120 is immersed in the diluent. Next, the nonwoven fabric 120 is dehydrated and dried to manufacture the air filter 110.

[0120] Hereinafter, a method for manufacturing an air filter will be described in detail.

[0121] [Preparation of nonwoven fabric]

[0122] First, prepare a 1.1 ml / cm 2 / sec~40ml / cm 2 Specifically, in a state where a water-repellent and oil-repellent film described later is formed on the fiber surface of the nonwoven fabric, a nonwoven fabric having an air permeability of 1 ml / cm 2 / sec~30ml / cm 2 When the water-repellent and oil-repellent film is formed as a thick film, a nonwoven fabric with high air permeability is selected, and when the water-repellent and oil-repellent film is formed as a thin film, a nonwoven fabric with low air permeability is selected.

[0123] The material of the nonwoven fabric is the same as that of the nonwoven fabric of the first embodiment. As nonwoven fabrics, for example, there are cellulose mixed ester membrane filters, glass fiber filter paper, and nonwoven fabrics made by mixing polyethylene terephthalate fibers and glass fibers (manufactured by Anji Filter Paper Co., Ltd., trade name: 340). In this way, the nonwoven fabric is made of one or more fibers selected from polyethylene terephthalate (PET), polypropylene (PP), polytetrafluoroethylene (PTFE), glass, alumina, carbon, cellulose, pulp, nylon and metal. The fiber can also be a fiber mixed with two or more fibers. In order to obtain the above-mentioned air permeability, the thickness of the fiber (fiber diameter) is preferably 0.01μm to 10μm. Regarding the thickness of the nonwoven fabric, when the air filter is a single layer, it is preferably 0.2mm to 0.8mm, and when the air filter is a multi-layer laminate, the thickness of the laminate is preferably 0.2mm to 1.6mm. When the main component of the water-repellent and oil-repellent film-forming material of the present invention is silica sol-gel, in order to obtain close contact with the fiber, the fiber is preferably a material having a hydroxyl group. Among them, glass, alumina, cellulose nanofibers, etc. also have a thin fiber diameter, which can make the air permeability a low value within the above range.

[0124] As mentioned above, in the case of nonwoven fabrics, Figure 5In the case of a laminated body formed by stacking multiple non-woven fabrics 130, 140 as shown, by making the fibers of the non-woven fabric 130 on the side where air containing oil mist and dust flows in glass fibers, the water-repellent and oil-repellent film containing silica sol gel as the main component is more firmly bonded to the glass fibers and is difficult to peel off from the fibers of the non-woven fabric.

[0125] [Method for producing a water- and oil-repellent film-forming liquid composition]

[0126] [Preparation of oxide particle dispersion]

[0127] First, a dispersion of oxide particles is prepared by dispersing the oxide particles in an organic solvent. As organic solvents, methanol, ethanol, isopropanol (hereinafter, sometimes referred to as IPA), tetrahydrofuran, hexane, chloroform, toluene, ethyl acetate, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), acetone, fluorine-based solvents, etc. can be exemplified. Among them, alcohols such as methanol, ethanol, and isopropanol having a boiling point lower than 120°C and a carbon number in the range of 1 to 4 are preferred. As oxide particles, particles of SiO2, Al2O3, MgO, CaO, TiO2, ZnO, and ZrO2, their mixed particles, composite oxide particles, etc. can be exemplified.

[0128] [Preparation of Fluorine-Containing Oxygen Particle Dispersion]

[0129] Next, a fluorine-containing compound containing a fluorine-containing functional group component represented by the above formula (1) or formula (2) is added to the prepared dispersion of the oxide particles to synthesize a composite material obtained by nanocompositing the oxide particles and the fluorine-containing functional group component. In addition, water and a catalyst are added to promote the reaction. Thus, a dispersion of fluorine-containing oxide particles is prepared.

[0130] As the above-mentioned catalyst, organic acid, inorganic acid or titanium compound can be cited. As organic acid, formic acid and oxalic acid can be exemplified. As inorganic acid, hydrochloric acid, nitric acid and phosphoric acid can be exemplified. As titanium compound, tetrapropoxy titanium, tetrabutoxy titanium, tetraisopropoxy titanium and lactic acid titanium can be exemplified. The catalyst is not limited to the above-mentioned substances. In order to prevent the mixing of impurities, ion exchange water or pure water is preferably used as the above-mentioned water.

[0131] The fluorine-containing compound containing a fluorine-containing functional group component is represented by the above formula (3) or formula (4). As the perfluoroether group in these formulas (3) or (4), more specifically, the perfluoroether structure shown in the above formulas (5) to (13) can be cited. As a specific example of a fluorine-containing compound containing a fluorine-containing functional group component represented by the above formula (3) or (4) and having a perfluoroether structure, for example, the structure shown in the above formulas (19) to (27) can be cited.

[0132] As described above, the fluorine-based compound contained in the liquid composition for forming a water- and oil-repellent film of the second embodiment is the same as the fluorine-based compound described in the first embodiment, and has a perfluoroether group in the molecule, and the perfluoroether group is bonded to an oxygen atom with a plurality of short-chain perfluoroalkyl and perfluoroalkylene groups having a carbon number of 6 or less, and the fluorine content in the molecule is relatively high, so that the formed film can be given excellent water- and oil-repellent properties.

[0133] [Preparation of Silica Sol-Gel Solution]

[0134] First, a mixed solution is prepared by mixing tetramethoxysilane or tetraethoxysilane as a silicon alkoxide, an alcohol having a boiling point lower than 120°C and a carbon number in the range of 1 to 4, and water. At this time, an epoxy-containing silane that will become an alkylene component may also be mixed together. As the silicon alkoxide, specifically, tetramethoxysilane, its oligomer or tetraethoxysilane, its oligomer may be cited. For example, in order to obtain a highly durable water- and oil-repellent film, tetramethoxysilane is preferably used. On the other hand, in order to avoid the methanol produced during hydrolysis, tetraethoxysilane is preferably used.

[0135] Specific examples of the epoxy-containing silane serving as the alkylene component and the content ratio thereof are the same as the specific examples of the alkylene component and the content ratio thereof described in the first embodiment.

[0136] The alcohol having a boiling point lower than 120° C. and a carbon number of 1 to 4 is also the same as the alcohol described in the first embodiment. As described in the first embodiment, the mixed solution is prepared by adding an alcohol having a carbon number of 1 to 4 and water to silicon alkoxide or to silicon alkoxide and epoxy-containing silane, and stirring at a temperature of preferably 10° C. to 30° C. for 5 to 20 minutes.

[0137] The same catalyst as that described in the first embodiment is added and mixed into the mixed solution prepared by the method described in the first embodiment. Thus, a silica sol-gel solution is prepared. For the next step, alcohol is added and mixed into the silica sol-gel solution.

[0138] When the silica sol-gel solution is set to 100 mass %, the silica sol-gel solution to which the alcohol is added and mixed contains silicon alkoxide at a ratio of 2 mass % to 50 mass %, an alcohol having a carbon number in the range of 1 to 4 at a ratio of 20 mass % to 98 mass %, water at a ratio of 0.1 mass % to 40 mass %, and a catalyst at a ratio of 0.01 mass % to 5 mass %. In the case of mixing an epoxy-containing silane as an alkylene component, the epoxy-containing silane is contained at most at a ratio of 30 mass %.

[0139] The reason why the ratio of the alcohol having 1 to 4 carbon atoms and the ratio of water are limited to the above ranges is the same as the reason described in the first embodiment.

[0140] The range of SiO 2 concentration (SiO 2 amount) when the silica sol-gel is assumed to be 100 mass % and the reason for it are the same as those described in the first embodiment.

[0141] Specific examples of the above-mentioned catalyst and the content ratio thereof are the same as the specific examples and the content ratio thereof described in the first embodiment.

[0142] [Water- and oil-repellent film-forming liquid composition]

[0143] The second embodiment of the water-repellent and oil-repellent film-forming liquid composition is manufactured by the above-mentioned manufacturing method, comprising oxide particles, silica sol-gel and solvent bonded with the above-mentioned fluorine-containing functional group component. The fluorine-containing functional group component has a perfluoroether structure shown in the above formula (1) or formula (2), and when the water-repellent and oil-repellent film-forming liquid composition is set to 100 mass%, it contains 1 mass% to 30 mass% of the fluorine-containing functional group component.

[0144] The solvent is a mixed solvent of water and an alcohol having 1 to 4 carbon atoms, or a mixed solvent of water, an alcohol having 1 to 4 carbon atoms and an organic solvent other than the alcohol. Specific examples of the perfluoroether structure include the structures represented by the above formulae (19) to (27).

[0145] Since the water-repellent and oil-repellent film-forming liquid composition of the second embodiment includes a silica sol-gel liquid as a main component, and further includes oxide particles, it is possible to obtain a water-repellent and oil-repellent film having excellent adhesion to the fibers of a nonwoven fabric and a high-strength water-repellent and oil-repellent film that is difficult to peel off. In addition, since the water-repellent and oil-repellent film-forming liquid composition includes a fluorinated functional group component of a perfluoroether structure shown in the above formula (1) or formula (2), it has an oil-repellent effect. If the fluorinated functional group component is less than 1% by mass when the water-repellent and oil-repellent film is set to 100% by mass, the formed film cannot be given oil repellency. If it exceeds 30% by mass, the film-forming property is poor due to the repulsion of the film. The content ratio of the fluorinated functional group component is preferably 2% to 28% by mass.

[0146] [Method for forming a water- and oil-repellent film on the fiber surface of a nonwoven fabric]

[0147] The method for forming a water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric of the second embodiment is the same as the method described in the first embodiment. Figure 4As shown in the enlarged view at the center of the nonwoven fabric 120, a water-repellent and oil-repellent film 121 is formed on the surface of the fiber 120c constituting the nonwoven fabric 120. When the amount of liquid removal is small, the water-repellent and oil-repellent film is formed on the fiber surface of the nonwoven fabric in the form of a thick film, and when the amount of liquid removal is large, the water-repellent and oil-repellent film is formed on the fiber surface of the nonwoven fabric in the form of a thin film.

[0148] <Third Embodiment>

[0149] [Air filter]

[0150] like Figure 7 As shown, the air filter 210 of the third embodiment includes a nonwoven fabric 220 and a water-repellent and oil-repellent film 221 formed on the fiber surface of the nonwoven fabric. The nonwoven fabric 220, which is a main component of the air filter 210, has a side 220a into which air containing oil mist and dust flows and another side 220b opposite to the side 220a from which the air flows out, and the nonwoven fabric 220 is composed of a single layer. Figure 8 As shown, the air filter 250 may also be composed of a double-layer laminate of an upper nonwoven fabric 230 and a lower nonwoven fabric 240. In this case, the upper surface of the upper nonwoven fabric 230 becomes a side 230a into which the air containing oil mist and dust flows, and the lower surface of the lower nonwoven fabric 240 becomes the other side 240b opposite to the side 230a. In addition, the laminate is not limited to a double layer, and may also be composed of multiple layers such as three layers and four layers.

[0151] like Figure 7 As shown in the enlarged view of the center of the nonwoven fabric 220, the nonwoven fabric 220 is formed by entanglement of a plurality of fibers 220c, and pores 220d are formed between the fibers. The pores 220d penetrate between one side 220a and the other side 220b of the nonwoven fabric 220. A water-repellent and oil-repellent film 221 is formed on the surface of the fibers 220c of the nonwoven fabric. The unit weight of the nonwoven fabric is preferably 200 g / m 2 ~400g / m 2 , but is not limited to this range. The water-repellent and oil-repellent film 221 comprises oxide particles B having an average particle size of 2 nm to 90 nm and a silica sol gel C. The oxide particles B are bonded with a first fluorine-containing functional group component A1 represented by the aforementioned formula (1) or (2). In addition, the silica sol gel C comprises a second fluorine-containing functional group component A2 represented by the aforementioned formula (1) or (2). When the water-repellent and oil-repellent film 221 is set to 100 mass %, the first fluorine-containing functional group component A1 and the second fluorine-containing functional group component A2 are contained in a total ratio of 1 mass % to 30 mass %. In addition, the mass ratio C:B of the silica sol gel C to the oxide particles B is in the range of 10:90 to 90:10.

[0152] like Figure 7As shown in the further enlarged view of the upper part of the water-repellent and oil-repellent film 221, a plurality of oxide particles 221a whose particle surfaces are covered with fluorine-containing functional group components are bonded by using a fluorine-containing silica sol-gel 221b as an adhesive. Since the water-repellent and oil-repellent film 221 includes oxide particles 221a, a thick film is formed in appearance, which can narrow the pores 220d between fibers. In addition, the film thickness can be controlled by changing the particle size of the oxide particles and the content ratio of the oxide particles in the film components.

[0153] If the unit area weight of the non-woven fabric is less than 200g / m 2 If the fiber pores are too large, the dust collection capacity will be insufficient. 2 , since the air permeability is less than 1ml / cm 2 / second, dust is easy to immediately block the pores between fibers or the air permeability is too low, so the air filter is prone to pressure loss due to the resistance of air sent into the air filter, and the efficiency of air supply energy is easy to deteriorate. The unit area weight of nonwoven fabric is more preferably 200g / m 2 ~350g / m 2 within the range.

[0154] In the state of the air filter 210 with the water-repellent and oil-repellent film 221 formed on the fiber surface, the nonwoven fabric 220 is manufactured to have a 1 ml / cm 2 / sec~30ml / cm 2 / second air permeability. If the air permeability is less than 1ml / cm 2 / sec, when the nonwoven fabric is immersed in the diluent of the water-repellent and oil-repellent film-forming liquid composition described later, the diluent is difficult to penetrate into the nonwoven fabric, and the water-repellent and oil-repellent film 221 cannot be fully formed on the fiber surface. In addition, the air permeability is poor, and the air containing oil mist and dust is difficult to pass through. If it exceeds 30ml / cm 2 / second, although the water-repellent and oil-repellent film 221 is fully formed on the fiber surface, the size of the pores 220d of the nonwoven fabric is much larger than the particle sizes of the oil particles 222 and dust particles 223 in the oil mist in the inflowing air, and the oil particles 222 and dust particles 223 pass through the pores of the nonwoven fabric together with the air and pass through the air filter 210, and the oil mist and dust cannot be captured. In other words, the oil repellent property cannot be exerted. The air permeability is preferably 1.5ml / cm 2 / sec~25ml / cm 2 / sec. The air permeability was measured using a Frazier-type tester described in JIS-L1913:2000.

[0155] If the total content ratio of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 when the water-repellent and oil-repellent film 221 is set to 100% by mass is less than 1% by mass, the oil-repellent effect is lacking, and the performance of repelling oil mist is insufficient. That is, when the oil mist reaches the air filter, the oil mist wets and expands on the fiber surface, and it is easy to block the pores 220d. In addition, if the total content ratio exceeds 30% by mass, the adhesion of the water-repellent and oil-repellent film to the nonwoven fabric deteriorates. The total content ratio of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 when the water-repellent and oil-repellent film 221 is set to 100% by mass is preferably 5% to 25% by mass.

[0156] The average particle size of the oxide particles B contained in the water-repellent and oil-repellent film 221 is in the range of 2nm to 90nm. Preferably, it is in the range of 2nm to 85nm. If the average particle size is less than 2nm, it is easy to cause the aggregation of the oxide particles and it is difficult to disperse in the medium. If it exceeds 90nm, it is difficult for the oxide particles B to adhere to the fiber surface of the non-woven fabric and it is easy to fall off from the water-repellent and oil-repellent film. The mass ratio C:B of the silica sol gel C and the oxide particles B is in the range of 10:90 to 90:10. That is, when the total amount of the silica sol gel C and the oxide particles B is set to 100% by mass, when the silica sol gel C is less than 10% by mass and the oxide particles B exceed 90% by mass, the binder component in the water-repellent and oil-repellent film is too little, and the water-repellent and oil-repellent film is easily peeled off from the fiber surface of the non-woven fabric. On the contrary, when the oxide particles B are less than 10% by mass and the silica sol gel C exceeds 90% by mass, the oxide particles are too little, and the water-repellent and oil-repellent film is easily peeled off from the fiber surface of the non-woven fabric. The preferred mass ratio C:B is 20:80 to 80:20.

[0157] This air filter 210 plays the same role as the air filter described in the first embodiment. Figure 7As shown, the air containing oil mist and dust reaches one side 220a of the nonwoven fabric 220 constituting the air filter 210. Here, since the air filter 210 has a predetermined air permeability and the water-repellent and oil-repellent film 221 exhibits oil repellency, the oil particles 222 of the oil mist cannot pass through the air filter 210 even when the particle size is larger than the pore size of the pore 220d, and even when the particle size is slightly smaller than the pore size of the pore 220d, the oil particles 222 are only repelled by the water-repellent and oil-repellent film 221 between the fibers 220c and 220c of the nonwoven fabric 220 and attached to the water-repellent and oil-repellent film 221. At the same time, the dust particles 223 are also only attached to the water-repellent and oil-repellent film 221. Since the water-repellent and oil-repellent film 221 contains oxide particles 221a, the film becomes uneven, and the oil particles 222 are less attached to the film, while the dust particles 223 are easily attached. Thus, the oil particles 222 and dust particles 223 of the oil mist are captured by the nonwoven fabric, and the air containing the oil mist and dust passes through the air gap formed in the Figure 7 As shown in the enlarged view, the pores 220d between the fibers 220c reach the other side 220b, become air without oil mist and dust, and pass through the non-woven fabric 220.

[0158] If the air filter is continued to be used and the amount of oil mist captured inside the nonwoven fabric is increased, then when the air filter is horizontally configured, the oil mist with a low degree of attachment to the film is accompanied by the air passing through in a liquefied form and gathered on the other side of the air filter, and when the air filter is vertically configured, the captured oil mist is gathered at the lower end of the air filter due to its own weight and will not block the pores of the nonwoven fabric. Thus, the pore blockage caused by the oil mist can be suppressed. Dust is directly attached to the water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric, or is attached to the oil mist attached to the water-repellent and oil-repellent film. By regularly utilizing a pneumatic shaker, etc., the air filter 210 is impacted, so that the oil mist and dust accumulated in the nonwoven fabric 220 can be removed from the air filter 210.

[0159] [Manufacturing method of air filter]

[0160] The air filter is generally manufactured by the following method.

[0161] like Fig. 9 As shown, the oxide particle dispersion is prepared by mixing oxide particles and an organic solvent. A fluorine-containing compound containing a first fluorine-containing functional group component A1 is mixed in the dispersion, and water and a catalyst are further mixed to prepare a dispersion of fluorine-containing oxide particles. On the other hand, a liquid of fluorine-containing silica sol-gel C is prepared by mixing silicon alkoxide, alcohol, a fluorine-containing compound containing a second fluorine-containing functional group component A2 and water and mixing an alkylene component as needed, and adding a catalyst to the mixed solution.

[0162] A liquid composition for forming a water-repellent and oil-repellent film is prepared by mixing a solvent in the liquid of the silica sol gel C and mixing the mixed liquid with the dispersion of the fluorine oxide particles. The liquid composition is diluted with a solvent to prepare a diluted liquid, and the nonwoven fabric 220 is immersed in the diluted liquid. Next, the nonwoven fabric 220 is dehydrated and dried to manufacture the air filter 210.

[0163] Hereinafter, a method for manufacturing an air filter will be described in detail.

[0164] [Preparation of nonwoven fabric]

[0165] First, prepare a 1.1 ml / cm 2 / sec~40ml / cm 2 Specifically, in a state where a water-repellent and oil-repellent film described later is formed on the fiber surface of the nonwoven fabric, a nonwoven fabric having an air permeability of 1 ml / cm 2 / sec~30ml / cm 2 When the water-repellent and oil-repellent film is formed as a thick film, a nonwoven fabric with high air permeability is selected, and when the water-repellent and oil-repellent film is formed as a thin film, a nonwoven fabric with low air permeability is selected.

[0166] The material of the nonwoven fabric is the same as that of the nonwoven fabric of the first embodiment. As nonwoven fabrics, for example, there are cellulose mixed ester membrane filters, glass fiber filter paper, and nonwoven fabrics made by mixing polyethylene terephthalate fibers and glass fibers (manufactured by Anji Filter Paper Co., Ltd., trade name: 340). In this way, the nonwoven fabric is made of one or more fibers selected from polyethylene terephthalate (PET), polypropylene (PP), polytetrafluoroethylene (PTFE), glass, alumina, carbon, cellulose, pulp, nylon and metal. The fiber can also be a fiber mixed with two or more fibers. In order to obtain the above-mentioned air permeability, the thickness of the fiber (fiber diameter) is preferably 0.01μm to 10μm. Regarding the thickness of the nonwoven fabric, when the air filter is a single layer, it is preferably 0.2mm to 0.8mm, and when the air filter is a multi-layer laminate, the thickness of the laminate is preferably 0.2mm to 1.6mm. When the main component of the water-repellent and oil-repellent film-forming material of the present invention is silica sol-gel, in order to obtain close contact with the fiber, the fiber is preferably a material having a hydroxyl group. Among them, glass, alumina, cellulose nanofibers, etc. also have a thin fiber diameter, which can make the air permeability a low value within the above range.

[0167] As mentioned above, in the case of nonwoven fabrics, Figure 8In the case of a laminated body formed by stacking multiple non-woven fabrics 230, 240 as shown, by making the fibers of the non-woven fabric 230 on the side where air containing oil mist and dust flows in glass fibers, the water-repellent and oil-repellent film containing silica sol gel as the main component is more firmly bonded to the glass fibers and is difficult to peel off from the fibers of the non-woven fabric.

[0168] [Method for producing a water- and oil-repellent film-forming liquid composition]

[0169] [Preparation of oxide particle dispersion]

[0170] First, a dispersion of oxide particles is prepared by dispersing the oxide particles in an organic solvent. As organic solvents, methanol, ethanol, isopropanol (hereinafter, sometimes referred to as IPA), tetrahydrofuran, hexane, chloroform, toluene, ethyl acetate, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), acetone, fluorine-based solvents, etc. can be exemplified. Among them, alcohols such as methanol, ethanol, and isopropanol having a boiling point lower than 120°C and a carbon number in the range of 1 to 4 are preferred. As oxide particles, particles of SiO2, Al2O3, MgO, CaO, TiO2, ZnO, and ZrO2, their mixed particles, composite oxide particles, etc. can be exemplified.

[0171] [Preparation of Fluorine-Containing Oxygen Particle Dispersion]

[0172] Next, a fluorine-containing compound containing the first fluorine-containing functional group component A1 shown in the above formula (1) or formula (2) is added to the prepared oxide particle dispersion to synthesize a composite material obtained by nanocompositing the oxide particles and the fluorine-containing functional group component. In addition, water and a catalyst are added to promote the reaction. Thus, a dispersion of fluorine-containing oxide particles is prepared.

[0173] As the above-mentioned catalyst, organic acid, inorganic acid, alkali or titanium compound can be cited, formic acid and oxalic acid can be exemplified as organic acid, hydrochloric acid, nitric acid and phosphoric acid can be exemplified as inorganic acid, sodium hydroxide, lithium hydroxide, magnesium hydroxide, potassium hydroxide, calcium hydroxide and ammonia can be exemplified as alkali, tetrapropoxy titanium, tetrabutoxy titanium, tetraisopropoxy titanium and titanium lactate can be exemplified as titanium compound. The catalyst is not limited to the above-mentioned substances. In order to prevent the mixing of impurities, it is best to use ion exchange water or pure water as the above-mentioned water.

[0174] The fluorine-based compound containing the first fluorine-containing functional group component A1 is represented by the above formula (3) or formula (4). As the perfluoroether group in these formulas (3) or (4), more specifically, the perfluoroether structure shown in the above formulas (5) to (13) can be cited. As a specific example of a fluorine-based compound containing a fluorine-containing functional group component represented by the above formula (3) or (4) and having a perfluoroether structure, for example, the structures shown in the above formulas (19) to (27) can be cited.

[0175] [Preparation of fluorine-containing silica sol-gel solution]

[0176] First, a mixed solution is prepared by mixing tetramethoxysilane or tetraethoxysilane as a silicon alkoxide, an alcohol having a boiling point lower than 120°C and a carbon number in the range of 1 to 4, a fluorine-based compound containing the second fluorine-containing functional group component A2 represented by the above formula (1) or formula (2), and water. At this time, an epoxy-containing silane that will become an alkylene component may also be mixed together. Specifically, as the silicon alkoxide, tetramethoxysilane (TMOS), its oligomers or tetraethoxysilane (TEOS), its oligomers can be cited. For example, in order to obtain a highly durable water- and oil-repellent film, it is preferred to use tetramethoxysilane. On the other hand, in order to avoid the methanol produced during hydrolysis, it is preferred to use tetraethoxysilane.

[0177] The second fluorine-containing functional group component A2 contained in the fluorine-containing compound is represented by the above formula (1) or (2), and the specific fluorine-containing compound containing the first fluorine-containing functional group component A1 and the specific fluorine-containing compound containing the second fluorine-containing functional group component A2 may be the same or different.

[0178] Specific examples of the epoxy-containing silane serving as the alkylene component and the content ratio thereof are the same as the specific examples of the alkylene component and the content ratio thereof described in the first embodiment.

[0179] The alcohol having a boiling point lower than 120° C. and a carbon number of 1 to 4 is also the same as the alcohol described in the first embodiment. As described in the first embodiment, the mixed solution is prepared by adding an alcohol having a carbon number of 1 to 4 and water to silicon alkoxide or to silicon alkoxide and epoxy-containing silane, and stirring at a temperature of preferably 10° C. to 30° C. for 5 to 20 minutes.

[0180] The same catalyst as that described in the first embodiment is added and mixed into the mixed solution prepared by the method described in the first embodiment. Thus, a fluorine-containing silica sol-gel solution is prepared. In addition, alcohol may be added and mixed into the fluorine-containing silica sol-gel solution for the next step.

[0181] When the alcohol is added and mixed, the fluorine-containing silica sol-gel solution preferably contains silicon alkoxide at a ratio of 2% to 50% by mass, an alcohol having a carbon number of 1 to 4 at a ratio of 20% to 98% by mass, water at a ratio of 0.1% to 40% by mass, and a catalyst at a ratio of 0.01% to 5% by mass, when the fluorine-containing silica sol-gel solution is set to 100% by mass. When the epoxy-containing silane is mixed as an alkylene component, it is preferred that the epoxy-containing silane is contained at a maximum of 30% by mass.

[0182] The reason why the ratio of the alcohol having 1 to 4 carbon atoms and the ratio of water are limited to the above ranges is the same as the reason described in the first embodiment.

[0183] The range of SiO 2 concentration (SiO 2 amount) when the silica sol-gel is assumed to be 100 mass % and the reason for it are the same as those described in the first embodiment.

[0184] Specific examples of the above-mentioned catalyst and the content ratio thereof are the same as the specific examples and the content ratio thereof described in the first embodiment.

[0185] [Water- and oil-repellent film-forming liquid composition]

[0186] The liquid composition for forming a water-repellent and oil-repellent film of the third embodiment is manufactured by the above-mentioned manufacturing method, comprising oxide particles B bonded with the above-mentioned first fluorine-containing functional group component A1, a silica sol gel C containing the above-mentioned second fluorine-containing functional group component A2, and a solvent. As a solvent, water, methanol, ethanol, isopropanol (hereinafter, sometimes referred to as IPA), tetrahydrofuran, hexane, chloroform, toluene, ethyl acetate, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), acetone, fluorine-based solvents, etc. can be exemplified. These fluorine-containing functional group components A1 and A2 have a perfluoroether structure shown in the above formula (1) or formula (2), and when the total amount of components other than the solvent is set to 100% by mass, and when the liquid composition is set to 100% by mass, a total of 1% to 30% by mass of fluorine-containing functional group components A1 and A2 are contained. The reason for setting the total containing ratio to the above-mentioned numerical range is as described above.

[0187] It is preferred that the mass ratio of the first fluorinated functional group component A1 to the second fluorinated functional group component A2 is the same or the first fluorinated functional group component A1 is contained in a larger amount than the second fluorinated functional group component A2 because the adhesion of the water- and oil-repellent film to the fiber surface of the nonwoven fabric is improved.

[0188] As described above, since the fluorine compound contained in the water-repellent and oil-repellent film-forming liquid composition of the third embodiment has a perfluoroether group in the molecule, the perfluoroether group is bonded to a plurality of perfluoroalkyl and perfluoroalkylene groups with a short chain length of less than 6 carbon atoms on an oxygen atom, and the fluorine content in the molecule is high, it is possible to impart excellent water-repellent and oil-repellent properties to the formed film. As a specific example of the perfluoroether structure, the structures shown in the above formulas (19) to (27) can be cited.

[0189] In addition, the mass ratio C:B of the silica sol gel C and the oxide particles B of the liquid composition for forming a water-repellent and oil-repellent film of the third embodiment is preferably in the range of 10:90 to 90:10. That is, when the total amount of silica sol gel C and oxide particles B is set to 100% by mass, when the silica sol gel C is less than 10% by mass and the oxide particles B exceed 90% by mass, the binder component in the liquid composition is too small, and the formed film is easily peeled off from the fiber surface of the non-woven fabric. On the contrary, when the oxide particles B are less than 10% by mass and the silica sol gel C exceeds 90% by mass, the oxide particles are too small, and the film is easily peeled off from the fiber surface of the non-woven fabric. The more preferred mass ratio C:B is 20:80 to 80:20.

[0190] Since the liquid composition for forming a water-repellent and oil-repellent film of the third embodiment comprises a dispersion of fluorine oxide particles and a fluorine-containing silica sol-gel liquid, when forming a film on the fiber surface of a non-woven fabric, it can impart better oil-repellent properties than conventional liquid compositions, and can obtain a high-strength water-repellent and oil-repellent film that has excellent adhesion to the fiber surface of the non-woven fabric and is difficult to peel off.

[0191] [Method for forming a water- and oil-repellent film on the fiber surface of a nonwoven fabric]

[0192] The method for forming a water-repellent and oil-repellent film on the fiber surface of the nonwoven fabric of the third embodiment is the same as the method described in the first embodiment. Figure 7 As shown in the enlarged view at the center of the nonwoven fabric 220, a water-repellent and oil-repellent film 221 is formed on the surface of the fiber 220c constituting the nonwoven fabric 220. When the amount of liquid removal is small, the water-repellent and oil-repellent film is formed on the fiber surface of the nonwoven fabric in the form of a thick film, and when the amount of liquid removal is large, the water-repellent and oil-repellent film is formed on the fiber surface of the nonwoven fabric in the form of a thin film.

[0193] Example

[0194] Hereinafter, examples of the present invention will be described in detail together with comparative examples.

[0195] First, Examples 1 to 6 of the air filter corresponding to the first embodiment will be described, and Comparative Examples 1 to 5 of the air filter not corresponding to the first embodiment will be described.

[0196] Next, Synthesis Examples 1 to 9 and Comparative Synthesis Examples 1 to 3 for preparing dispersions of oxide particles corresponding to the second embodiment are described, followed by a description of Examples 7 to 15 and Comparative Examples 6 to 9 related to the preparation of liquid compositions for forming water- and oil-repellent films and the manufacture of air filters using these synthesis examples and comparative synthesis examples.

[0197] In addition, Synthesis Examples 10 to 18 and Comparative Synthesis Examples 4 to 5 for preparing a dispersion of oxide particles corresponding to the third embodiment are described, followed by a description of Synthesis Examples 19 to 22 and Comparative Synthesis Example 6 for preparing a fluorine-containing silica sol-gel solution, followed by a description of Examples 16 to 24 and Comparative Examples 10 to 18 related to the manufacture of air filters using these synthesis examples and comparative synthesis examples.

[0198] <Examples and Comparative Examples Corresponding to the First Embodiment>

[0199] <Example 1>

[0200] By mixing 8.52 g of a trimer to pentamer of tetramethoxysilane (TMOS) as a silicon alkoxide (manufactured by Mitsubishi Chemical Corporation, trade name: MKC silicate MS51), 0.48 g of 3-glycidoxypropyltrimethoxysilane (GPTMS: manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM-403) as an epoxy-containing silane as an alkylene component, 0.24 g of a fluorine-containing silane (R: ethyl) represented by formula (19) as a fluorine-containing functional group component, and 17.34 g of ethanol (EtOH) (boiling point 78.3° C.) as an organic solvent, and further adding 3.37 g of ion-exchanged water, stirring at a temperature of 25° C. in a separable flask for 5 minutes, a mixed solution was prepared. In addition, 0.05 g of hydrochloric acid with a concentration of 35% by mass was added to the mixed solution as a catalyst, and stirred at 40° C. for 2 hours. Thus, a liquid composition for forming a water-repellent and oil-repellent film containing a silica sol gel was prepared. The preparation contents are shown in Table 1.

[0201] [Table 1]

[0202]

[0203] When the silica sol gel is set to 100% by mass, the silica sol gel of the obtained water-repellent and oil-repellent film-forming liquid composition contains 4.5% by mass of fluorine-containing functional group components and 7.8% by mass of alkylene components with 7 carbon atoms. Then, 7.0g of industrial alcohol (manufactured by Japan Alcohol Industry Co., Ltd., AP-7) is added and mixed in 1.0g of the water-repellent and oil-repellent film-forming liquid composition as a solvent to prepare a dilution of the liquid composition. In this dilution, as a substrate for an air filter, a 5ml / cm 2 / second air permeability and the unit area weight of the single layer is 265g / m 2 The nonwoven fabric was immersed in the nonwoven fabric for 30 seconds. The base material of the air filter is a nonwoven fabric composed of PET fibers. The nonwoven fabric was pulled out of the dilution liquid, spread on a horizontal metal net, and left at room temperature for 30 minutes to deliquate. Then, the single-layer nonwoven fabric was placed in a dryer maintained at 120°C for 30 minutes to dry and obtain an air filter. The air permeability of the air filter is 3.0ml / cm 2 The above results are shown in Table 2.

[0204] [Table 2]

[0205]

[0206] <Examples 2 to 5, Comparative Examples 2 to 4>

[0207] For Examples 2 to 5 and Comparative Examples 2 to 4, as shown in Table 2, the type of air filter substrate and the type of fluorine-containing silane that becomes a fluorine-containing functional group component are selected, and the addition amount of TMOS, the addition amount of GPTMS and the addition amount of fluorine-containing silane shown in Example 1 are changed respectively. In addition, the liquid composition for forming a water-repellent and oil-repellent film of Examples 2 to 5 and Comparative Examples 2 to 4 is obtained in the same manner as Example 1. The same industrial alcohol as in Example 1 is added to these liquid compositions, and a diluent for impregnating the air filter substrate is prepared in the same manner as in Example 1. As in Example 1, the air filter substrate shown in Table 2 is immersed in these diluents and dried to obtain an air filter having the characteristics shown in Table 2. In addition, in Table 2, the R in the formula of the fluorine-containing silane that becomes a fluorine-containing functional group component and is represented by Formula (19) to Formula (23) is all ethyl.

[0208] In addition, the nonwoven fabric used in Example 3 is different from the nonwoven fabric in Example 1 and is composed of a double layer of glass fiber nonwoven fabric and PET fiber nonwoven fabric. The air permeability of the air filter is 1.2 ml / cm 2 In addition, the nonwoven fabrics used in Example 5 and Comparative Example 4 are different from those in Example 1 and are composed of mixed fibers of PET fibers and glass fibers (PET: glass = 80:20 by mass ratio). The air permeability of each air filter is 28.0 ml / cm 2 / sec and 0.5ml / cm 2 In addition, the air filter substrates used in Example 6 and Comparative Example 5 are different from the nonwoven fabric of Example 1 and are single-layer nonwoven fabrics composed of PTFE fibers. The air permeability of each air filter is 3.0 ml / cm 2 / sec and 5.0ml / cm 2 / Second.

[0209] <Comparative Example 1>

[0210] In Comparative Example 1, the same nonwoven fabric as in Example 1 was used, but the fluorine-containing silane as the fluorine-containing functional group component was not contained in the silica sol-gel.

[0211] <Comparative Example 5>

[0212] In Comparative Example 5, a commercially available 1 μm-mesh polytetrafluoroethylene (PTFE) membrane filter was used as an air filter substrate in an untreated state without being immersed in a diluted liquid of the water- and oil-repellent film-forming liquid composition as in Example 1.

[0213] <Comparative Test 1 and Evaluation>

[0214] To simulate the oil mist and dust flying from the machine tool using cutting fluid to process metal products, hexadecane and iron (III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were put into a rotating and revolving mixer at a mass ratio of 80:20 for stirring and mixing to obtain a simulated liquid. After 1 ml of the obtained simulated liquid was dripped from above onto 11 horizontally placed air filters obtained in Examples 1 to 6 and Comparative Examples 1 to 5, the air filter was vertically erected to confirm the falling property of the simulated liquid. The case where the simulated liquid penetrated into the air filter was set as the oil repellency of the air filter "poor", and the case where the simulated liquid fell from the air filter was set as the oil repellency of the air filter "good".

[0215] As can be seen from Table 2, in Comparative Example 1, since the silica sol-gel did not contain fluorine-containing silane as a fluorine-containing functional group component, the simulated liquid penetrated into the air filter without falling off, and the oil repellency was "poor".

[0216] In Comparative Example 2, since the content of the fluorine-containing functional group component was too high, namely 11.6% by mass, when the silica sol gel was taken as 100% by mass, the weight per unit area of ​​the nonwoven fabric was too low, namely 150 g / m 2 , so the air filter's air permeability is too high and is 60.0ml / cm 2 / second, the simulated liquid penetrates into the air filter without falling off, and its oil repellency is "poor".

[0217] In Comparative Example 3, the air permeability of the air filter was too high at 35 ml / cm 2 / second, the simulated liquid penetrates into the air filter without falling off, and its oil repellency is "poor".

[0218] In Comparative Example 4, although the simulated liquid fell from the air filter, the nonwoven fabric had a high weight per unit area of ​​450 g / m2. 2 , so the air filter's air permeability is too low and is 0.5ml / cm 2 / sec, the performance as an air filter is insufficient.

[0219] In Comparative Example 5, a PTFE membrane filter was used as the air filter, but the simulated liquid penetrated into the air filter without falling off, and the oil repellency was "poor".

[0220] In contrast, in the air filters of Examples 1 to 6, the weight per unit area of ​​the nonwoven fabric is 210 g / m 2 ~380g / m 2 In the range of 100 mass % of silica sol gel, the oil-repellent film having oil-repellent function contains the fluorine-containing functional group component at a ratio of 0.02 mass % to 9.8 mass %, and the air permeability of the air filter is 1.2 ml / cm 2 / sec~28.0ml / cm 2 / sec, which satisfies the scope of the invention of the first aspect, it can be confirmed that the simulated liquid falls from the air filter and the oil repellency thereof is all "good".

[0221] <Examples and Comparative Examples Corresponding to the Second Embodiment>

[0222] [Synthesis Examples 1 to 9 and Comparative Synthesis Examples 1 to 3 for Preparation of Oxide Particle Dispersion Liquid]

[0223] <Synthesis example 1>

[0224] To a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 12 nm (IPA-ST, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 9.75 g of the fluorine compound represented by the above formula (19) was added and mixed. Next, 3.51 g of water was added and mixed. In addition, 0.031 g of nitric acid was added and mixed at 40° C. for 2 hours to obtain a dispersion of silicon dioxide particles in which the fluorine compound was bonded to the silicon dioxide particles. The mass ratio A / B of the fluorine-containing functional group component A to the silicon dioxide as the oxide particle B was 0.61.

[0225] <Synthesis example 2>

[0226] Into a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 45 nm (IPA-ST-L, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 1.50 g of the fluorine compound represented by the above formula (20) was added and mixed. Next, 0.54 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide (Silica) particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B was 0.09.

[0227] <Synthesis example 3>

[0228] Into a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 80 nm (IPA-ST-ZL, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 0.75 g of the fluorine compound represented by the above formula (21) was added and mixed. Next, 0.27 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B was 0.05.

[0229] <Synthesis example 4>

[0230] Into a beaker containing 50.0 g of an IPA dispersion of the same silicon dioxide as in Synthesis Example 1, 2.25 g of the fluorine compound represented by the above formula (22) was added and mixed. Next, 0.81 g of water was added and mixed. In addition, 0.010 g of nitric acid was added, and a dispersion of silicon dioxide (Silica) particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B was 0.14.

[0231] <Synthesis example 5>

[0232] A dispersion of silica particles was obtained in the same manner as in Synthesis Example 4 except that the fluorine-based compound used in Synthesis Example 4 was replaced with the fluorine-based compound represented by the above formula (27). The mass ratio A / B was 0.14.

[0233] <Synthesis example 6>

[0234] Into a beaker containing 50.0 g of a methanol dispersion of zirconium dioxide having an average particle size of 3 nm (SZR-M, manufactured by Sakai Chemical Co., Ltd., ZrO2 concentration 30%), 11.25 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 4.05 g of water was added and mixed. In addition, 0.035 g of nitric acid was added, and a dispersion of zirconium dioxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B of the fluorine-containing functional group component A to the zirconium dioxide as the oxide particle B was 0.71.

[0235] <Synthesis Example 7>

[0236] Into a beaker containing 50.0 g of an IPA dispersion of titanium dioxide having an average particle size of 6 nm (TKD-701, manufactured by TAYCA, TiO2 concentration 18%), 2.70 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.97 g of water was added and mixed. In addition, 0.010 g of nitric acid was added, and a dispersion of titanium dioxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B of the fluorine-containing functional group component A to the titanium dioxide as oxide particles B was 0.28.

[0237] <Synthesis example 8>

[0238] Into a beaker containing 50.0 g of an IPA dispersion of aluminum oxide and silicon dioxide having an average particle size of 60 nm (Bai Lalu AS-L10, manufactured by Doki Chemical Co., Ltd., 3Al2O3·2SiO2 concentration 10%), 0.25 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.09 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of aluminum oxide and silicon dioxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B of the fluorine-containing functional group component A to the aluminum oxide and silicon dioxide as the oxide particles B was 0.05.

[0239] <Synthesis Example 9>

[0240] Into a beaker containing 50.0 g of an IPA dispersion of zinc oxide having an average particle size of 25 nm (MZ-500, manufactured by TAYCA, ZnO concentration 30%), 1.50 g of the fluorine-based compound represented by the above formula (27) was added and mixed. Next, 0.54 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of zinc oxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B of the fluorine-containing functional group component A to the zinc oxide as the oxide particle B was 0.09.

[0241] <Comparative Synthesis Example 1>

[0242] Into a beaker containing 50.0 g of an IPA dispersion of titanium dioxide having an average particle size of 230 nm (R32, manufactured by Sakai Chemical Co., Ltd., TiO2 concentration 30%), 1.50 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.54 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of titanium dioxide particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B of the fluorine-containing functional group component A to the titanium dioxide as oxide particles B was 0.09.

[0243] <Comparative Synthesis Example 2>

[0244] Into a beaker containing 50.0 g of an IPA dispersion of the same silicon dioxide as in Synthesis Example 1, 0.45 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.16 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide (Silica) particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B was 0.03.

[0245] <Comparative Synthesis Example 3>

[0246] Into a beaker containing 50.0 g of an IPA dispersion of the same silicon dioxide as in Synthesis Example 1, 15.00 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 5.40 g of water was added and mixed. In addition, 0.047 g of nitric acid was added, and a dispersion of silicon dioxide (Silica) particles was obtained in the same manner as in Synthesis Example 1. The mass ratio A / B was 0.95.

[0247] The contents of the dispersions of fluorine-containing oxide particles of Synthesis Examples 1 to 9 and Comparative Synthesis Examples 1 to 3 are shown in Table 3. In Table 3, all R in the fluorine-containing silanes represented by Formula (19) to Formula (22) and Formula (27) as fluorine-containing compounds are ethyl groups.

[0248] [Table 3]

[0249]

[0250] [Examples 7 to 15 and Comparative Examples 6 to 9 for preparing a liquid composition for forming a water- and oil-repellent film and producing an air filter]

[0251] <Example 7>

[0252] After mixing 30g of tetraethyl orthosilicate, 60g of ethanol and 10g of water, add 1g of nitric acid and mix at 30°C for 3 hours to obtain a silica sol gel solution. After adding 73.49g of industrial alcohol (AP-7, manufactured by Nippon Alcohol Industry Co., Ltd.) to 10.00g of the obtained silica sol gel solution and mixing, 11.51g of the dispersion of oxide particles of Synthesis Example 1 is added and mixed to obtain a liquid composition for forming a water-repellent and oil-repellent film. The obtained 10g of the liquid composition for forming a water-repellent and oil-repellent film is diluted with 100g of industrial alcohol to prepare a diluted solution. As the substrate of the air filter, a mixed fiber composed of PET fiber and glass fiber (PET: glass = 80:20 in mass ratio) and having an air permeability of 9.3ml / m 2 / s nonwoven fabric 356 manufactured by Anji Filter Paper Co., Ltd. The nonwoven fabric was immersed in the above dilution, excess liquid was removed, and dried at room temperature for 24 hours to produce a nonwoven fabric with an air permeability of 7.5 ml / cm 2 / second air filter. The contents are shown in the following Tables 4 and 5. In Table 4, "C / [A+B+C]×100" is the percentage (%) of the mass of the silica sol gel C relative to the total mass of the fluorine-containing functional group component A, the mass of the oxide particles B and the mass of the silica sol gel C, "[A+B] / [A+B+C]×100" is the percentage (%) of the total mass of the fluorine-containing functional group component A and the mass of the oxide particles B relative to the total mass of the fluorine-containing functional group component A, the mass of the oxide particles B and the mass of the silica sol gel C, and "A / [A+B+C]×100" is the percentage (%) of the mass of the fluorine-containing functional group component A relative to the total mass of the fluorine-containing functional group component A, the mass of the oxide particles B and the mass of the silica sol gel C.

[0253] [Table 4]

[0254]

[0255] (Note) A is a fluorine-containing functional group component, B is an oxide particle, and C is a silica sol-gel.

[0256] [Table 5]

[0257]

[0258] <Examples 8 to 15 and Comparative Examples 6 to 8>

[0259] For Examples 8 to 15 and Comparative Examples 6 to 8, as shown in Table 4, the type and weight of the dispersion liquid containing fluorine oxide particles, the weight of the silica sol-gel liquid, and the weight of the same industrial alcohol as in Example 7 were selected or determined.

[0260] Regarding the silica sol-gel solution, in Examples 8 to 15 and Comparative Examples 6 to 8, 28.50 g of a trimer to a pentamer of tetramethoxysilane (TMOS) (manufactured by Mitsubishi Chemical Corporation, trade name: MKC Silicate MS51) and 1.50 g of 3-glycidoxypropyltrimethoxysilane (GPTMS: manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM-403) as an epoxy-containing silane serving as an alkylene component were used instead of the ethyl orthosilicate used in Example 7. Other than this, the same operation as in Example 7 was performed.

[0261] In addition, as shown in Table 5, the types of nonwoven fabrics and air filter substrates having different air permeabilities were selected.

[0262] Moreover, in the same manner as in Example 7, water- and oil-repellent film-forming liquid compositions of Examples 8 to 15 and Comparative Examples 6 to 8 were obtained.

[0263] Furthermore, in the same manner as in Example 7, a nonwoven fabric was immersed in the diluted liquid of the water- and oil-repellent film-forming liquid composition, deliquescence was performed, and drying was performed to obtain an air filter having the air permeability shown in Table 5.

[0264] <Comparative Example 9>

[0265] In Comparative Example 9, a liquid composition for forming a water- and oil-repellent film was prepared by a method different from that of Examples 8 to 15 and Comparative Examples 6 to 8. That is, 8.52 g of a trimer to a pentamer of tetramethoxysilane (TMOS) as a silicon alkoxide (manufactured by Mitsubishi Chemical Corporation, trade name: MKC Silicate MS51), 0.48 g of 3-glycidoxypropyltrimethoxysilane (GPTMS: manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM-403) as an epoxy-containing silane serving as an alkylene component, 0.24 g of a fluorine-containing silane (R: ethyl) represented by Formula (27) as a fluorine-based compound, and 17.34 g of ethanol (EtOH) (boiling point 78.3° C.) as an organic solvent were mixed, and 3.37 g of ion-exchanged water was further added, and the mixture was stirred at 25° C. for 5 minutes in a separable flask to prepare a mixed solution. In addition, 0.05 g of hydrochloric acid with a concentration of 35% by mass was added to the mixed solution, and stirred at 40°C for 2 hours to obtain a fluorine-containing silica sol gel solution. 90 g of the same industrial alcohol as in Example 7 was mixed into 10 g of the silica sol gel solution, and 10 g of the IPA dispersion of silicon dioxide with an average particle size of 12 nm as in Synthesis Example 1 was added and mixed as a dispersion of oxide particles to prepare a liquid composition for forming a water-repellent and oil-repellent film. In the diluted solution of the liquid composition for forming a water-repellent and oil-repellent film, the same nonwoven fabric as in Example 15 was impregnated in the same manner as in Example 7, and the nonwoven fabric was dehydrated and dried to obtain an air filter having the characteristics shown in Table 5.

[0266] In addition, the nonwoven fabrics used in Example 15, Comparative Examples 8 and 9 are different from the nonwoven fabrics in Example 7 and are composed of a double layer of a nonwoven fabric of glass fiber and a nonwoven fabric of PET fiber. The air permeability of the air filters obtained by using the nonwoven fabrics used in Example 15, Comparative Examples 8 and 9 is 1.8 ml / cm 2 / sec, 1.4ml / cm 2 / sec and 0.8ml / cm 2 / Second.

[0267] <Comparative Test 2 and Evaluation>

[0268] The oil mist and dust flying from the machine tool using cutting fluid to process metal products were simulated, and the same simulated liquid as in one of the comparative tests was used. After 1 ml of the simulated liquid was dripped from above onto 13 horizontally placed air filters obtained in Examples 7 to 15 and Comparative Examples 6 to 9, the air filters were vertically erected to confirm the falling properties of the simulated liquid. The situation where the simulated liquid infiltrated the air filter was set as the oil repellency of the air filter to be "poor", and the situation where the simulated liquid fell from the air filter was set as the oil repellency of the air filter to be "good".

[0269] As shown in Table 5, since the air filter of Comparative Example 6 is prepared by the comparative synthesis example 1 containing the oxide (titanium dioxide) particles with an average particle size of 230nm to form a water-repellent and oil-repellent film, and nonwoven fabrics are impregnated in the liquid composition and deliquored and dried, the average particle size of the oxide particles is too large, and the silica sol as the binder component is difficult to make the oxide particles bonded to the fiber surface of the nonwoven fabric. As a result, the simulated liquid will not fall from the air filter, and the oil repellency is "poor".

[0270] In the air filter of Comparative Example 7, "A / B" is 0.03, "[A+B] / [A+B+C]×100" is 3%, and "A / [A+B+C]×100" is 0.1%. Since the content of the fluorine-containing functional group component in the water- and oil-repellent membrane is too small, the air permeability of the air filter is too high and is 33.3 ml / cm 2 / second, the simulated liquid penetrates into the air filter without falling off, and its oil repellency is "poor".

[0271] In the air filter of Comparative Example 8, "A / B" is 0.95, "[A+B] / [A+B+C]×100" is 82%, and "A / [A+B+C]×100" is 41.0%. Since the content of fluorinated functional group components in the water-repellent and oil-repellent membrane is too high, the simulated liquid will not fall from the air filter and the oil repellency is "poor".

[0272] In the air filter of Comparative Example 9, since a dispersion of oxide particles is added to the fluorine-containing silica sol-gel solution and mixed to prepare a liquid composition for forming a water-repellent and oil-repellent film, there are a plurality of oxide particles whose particle surfaces are lipophilic in the film, thereby greatly deteriorating the oil-repellent performance. As a result, the oil-repellent property is "poor". Since the air permeability of the air filter is too low and is 0.8 ml / cm 2 / second, so when used as an air filter, it is expected to be easily clogged.

[0273] In contrast, in the air filters of Examples 7 to 17, the fluorine-containing functional group component is of formula (1) or formula (2), the average particle size of the oxide particles is in the range of 2 nm to 90 nm, "A / [A+B+C]×100" is in the range of 1% to 30%, "[A+B] / [A+B+C]×100" is in the range of 5% to 80%, "A / B" is in the range of 0.05 to 0.80, and the air permeability of the air filter is 1 ml / cm 2 / sec~30ml / cm 2 / second, it was confirmed that the simulant liquid fell from the air filter and the oil repellency was all "good".

[0274] <Examples and Comparative Examples Corresponding to the Third Embodiment>

[0275] [Synthesis Examples 10 to 18 for Preparation of Oxide Particle Dispersion Liquid, Comparative Synthesis Examples 4 to 5]

[0276] <Synthesis example 10>

[0277] Into a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 12 nm (IPA-ST, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 1.50 g of the fluorine compound represented by the above formula (19) was added and mixed. Next, 0.10 g of water was added and mixed. In addition, 0.005 g of nitric acid was added and mixed at 40° C. for 2 hours to obtain a dispersion of silicon dioxide particles in which the fluorine compound was bonded to the silicon dioxide particles.

[0278] <Synthesis Example 11>

[0279] Into a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 45 nm (IPA-ST-L, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 1.50 g of the fluorine compound represented by the above formula (20) was added and mixed. Next, 0.10 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide particles was obtained in the same manner as in Synthesis Example 1.

[0280] <Synthesis Example 12>

[0281] Into a beaker containing 50.0 g of an IPA dispersion of silicon dioxide having an average particle size of 80 nm (IPA-ST-ZL, manufactured by Nissan Chemical Co., Ltd., SiO2 concentration 30%), 1.50 g of the fluorine compound represented by the above formula (21) was added and mixed. Next, 0.10 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide particles was obtained in the same manner as in Synthesis Example 1.

[0282] <Synthesis Example 13>

[0283] Into a beaker containing 50.0 g of the IPA dispersion of the same silicon dioxide as in Synthesis Example 12, 0.75 g of the fluorine compound represented by the above formula (22) was added and mixed. Next, 0.05 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0284] <Synthesis Example 14>

[0285] Into a beaker containing 50.0 g of the IPA dispersion of the same silicon dioxide as in Synthesis Example 12, 2.25 g of the fluorine compound represented by the above formula (23) was added and mixed. Next, 0.15 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of silicon dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0286] <Synthesis Example 15>

[0287] Into a beaker containing 50.0 g of a methanol dispersion of zirconium dioxide (SZR-M, manufactured by Sakai Chemical Co., Ltd., ZrO2 concentration 30%) having an average particle size of 3 nm, 8.00 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 4.05 g of water was added and mixed. In addition, 0.035 g of nitric acid was added, and a dispersion of zirconium dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0288] <Synthesis Example 16>

[0289] Into a beaker containing 50.0 g of an IPA dispersion of titanium dioxide having an average particle size of 6 nm (TKD-701, manufactured by TAYCA, TiO2 concentration 18%), 2.70 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.97 g of water was added and mixed. In addition, 0.010 g of nitric acid was added, and a dispersion of titanium dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0290] <Synthesis Example 17>

[0291] Into a beaker containing 50.0 g of an IPA dispersion of aluminum oxide and silicon dioxide having an average particle size of 60 nm (Bai Lalu AS-L10, manufactured by Doki Chemical Co., Ltd., 3Al2O3·2SiO2 concentration 10%), 0.03 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.02 g of water was added and mixed. Furthermore, 0.005 g of nitric acid was added, and a dispersion of aluminum oxide and silicon dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0292] <Synthesis Example 18>

[0293] Into a beaker containing 50.0 g of an IPA dispersion of zinc oxide having an average particle size of 25 nm (MZ-500, manufactured by TAYCA, ZnO concentration 30%), 0.30 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.11 g of water was added and mixed. Furthermore, 0.005 g of nitric acid was added, and a dispersion of zinc oxide particles was obtained in the same manner as in Synthesis Example 10.

[0294] <Comparative Synthesis Example 4>

[0295] Into a beaker containing 50.0 g of an IPA dispersion of titanium dioxide having an average particle size of 230 nm (R32, manufactured by Sakai Chemical Co., Ltd., TiO2 concentration 30%), 0.75 g of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.27 g of water was added and mixed. In addition, 0.005 g of nitric acid was added, and a dispersion of titanium dioxide particles was obtained in the same manner as in Synthesis Example 10.

[0296] <Comparative Synthesis Example 5>

[0297] In a beaker containing 50.0 g of the same IPA dispersion as in Synthesis Example 10, 0.10 g of water was added and mixed without adding any fluorine compound. Furthermore, 0.005 g of nitric acid was added, and a dispersion of silica particles was obtained in the same manner as in Synthesis Example 10.

[0298] The following Table 6 shows the contents of the dispersions of fluorine oxide particles of Synthesis Examples 10 to 18 and Comparative Synthesis Example 4 and the dispersion of fluorine oxide particles not containing in Comparative Synthesis Example 5. In Table 6, all R in the formula of the fluorine-containing silane represented by Formula (19) to Formula (23) and Formula (27) as the fluorine-based compound is ethyl.

[0299] [Table 6]

[0300]

[0301] [Synthesis Examples 19 to 22 for Preparing Fluorine-Containing Silica Sol-Gel Solution, Comparative Synthesis Example 6]

[0302] <Synthesis Example 19>

[0303] Into a beaker containing 28.5 g of a trimer to pentamer of tetramethoxysilane (TMOS) (manufactured by Mitsubishi Chemical Corporation, trade name: MKC silicate MS51) and 59.7 g of ethanol, 0.24 g (0.8% by mass) of the fluorine-based compound represented by the above formula (27) was added and mixed. Next, 1.5 g of 3-glycidoxypropyltrimethoxysilane (GPTMS: manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM-403) as an epoxy-containing silane to become an alkylene component and 10 g of water were added and mixed. In addition, 0.1 g of nitric acid was added and mixed at 30° C. for 3 hours to obtain a fluorine-containing silica sol-gel solution.

[0304] <Synthesis example 20>

[0305] To a beaker containing 24.0 g of the trimer to pentamer of TMOS and 59.7 g of ethanol as in Synthesis Example 19, 0.06 g (0.2 mass %) of the fluorine compound represented by the above formula (27) was added and mixed. Next, 6.0 g of the same GPTMS as in Synthesis Example 19 and 10 g of water were added as an alkylene component and mixed. Furthermore, 0.1 g of nitric acid was added and mixed at 30° C. for 3 hours to obtain a fluorine-containing silica sol-gel solution.

[0306] <Synthesis Example 21>

[0307] To a beaker containing 29.8 g of the same trimer to pentamer of TMOS as in Synthesis Example 19 and 59.8 g of ethanol, 3.00 g (10.0 mass %) of the fluorine compound represented by the above formula (27) was added and mixed. Next, 0.2 g of the same GPTMS as in Synthesis Example 19 and 10 g of water were added as an alkylene component and mixed. Furthermore, 0.1 g of nitric acid was added and mixed at 30° C. for 3 hours to obtain a fluorine-containing silica sol-gel solution.

[0308] <Synthesis example 22>

[0309] Into a beaker containing 30.0 g of tetraethoxysilane (TEOS, manufactured by Tokyo Chemical Industry Co., Ltd.) and 56.9 g of ethanol, 0.30 g (1.0 mass %) of the fluorine-based compound represented by the above formula (27) was added and mixed. Then, without adding an alkylene component, 10 g of water was added and mixed. In addition, 0.1 g of nitric acid was added and mixed at 30° C. for 3 hours to obtain a fluorine-containing silica sol gel solution.

[0310] <Comparative Synthesis Example 6>

[0311] In a beaker containing 28.5 g of the same TMOS trimer to pentamer as in Synthesis Example 11 and 59.6 g of ethanol, 1.5 g of GPTMS as in Synthesis Example 19 and 10 g of water were added as an alkylene component and mixed without adding any fluorine-based compound. Furthermore, 0.1 g of nitric acid was added and mixed at 30° C. for 3 hours to obtain a fluorine-free silica sol-gel solution.

[0312] The contents of the fluorine-containing silica sol-gel solutions of Synthesis Examples 19 to 22 and the fluorine-free silica sol-gel solution of Comparative Synthesis Example 6 are shown in Table 7 below.

[0313] [Table 7]

[0314]

[0315] [Examples 16 to 24 and Comparative Examples 10 to 18 for preparing a liquid composition for forming a water- and oil-repellent film and producing an air filter]

[0316] <Example 16>

[0317] To 6.4 g of the fluorine-containing silica sol-gel liquid obtained in Synthesis Example 19, 80.9 g of industrial alcohol (AP-7, manufactured by Nippon Alcohol Industry Co., Ltd.) as a solvent was added and mixed. Then, 5.2 g of the dispersion of the oxide particles of Synthesis Example 10 was added and mixed to prepare a liquid composition for forming a water-repellent and oil-repellent film. 85.0 g of the obtained liquid composition for forming a water-repellent and oil-repellent film was diluted with 15.0 g of a mixed solvent of water and industrial alcohol (water: industrial alcohol = 1: 1 in a mass ratio) to prepare a diluted solution. As a substrate for the air filter, a mixed fiber composed of PET fiber and glass fiber (PET: glass = 80: 20 in a mass ratio) and having an air permeability of 9.3 ml / m 2 / s nonwoven fabric 356 manufactured by Anji Filter Paper Co., Ltd. The nonwoven fabric was immersed in the above dilution, excess liquid was removed, and dried at room temperature for 24 hours to prepare a nonwoven fabric with an air permeability of 7.9 ml / cm 2 / sec air filter. The contents are shown in the following Tables 8 and 9. The contents are shown in the following Table 8.

[0318] [Table 8]

[0319]

[0320] (Note) A1 is the fluorine-containing functional group component bonded to the oxide particles, A2 is the fluorine-containing functional group component in the silica sol-gel, B is the oxide particles, and C is the silica sol-gel.

[0321] [Table 9]

[0322]

[0323] <Examples 17 to 24 and Comparative Examples 10 to 18>

[0324] As shown in Table 8, the type and weight of the dispersion liquid containing fluorine oxide particles, the type and weight of the fluorine-containing silica sol-gel liquid, and the weight of the solvent same as that in Example 1 were determined for Examples 17 to 24 and Comparative Examples 10 to 18, respectively, to prepare the liquid compositions for forming water- and oil-repellent films of Examples 17 to 24 and Comparative Examples 10 to 18.

[0325] Table 8 also shows the “total content ratio of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 in the liquid composition after the solvent is removed”, the “mass ratio of the silica sol gel C to the oxide particles B (C:B)” and the “mass ratio of the first fluorinated functional group component A1 to the second fluorinated functional group component A2 (A1:A2)”. In addition, the total content ratio (mass %) of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 in the liquid composition after the solvent is removed is the same as the total content ratio (mass %) of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 in the water- and oil-repellent film.

[0326] Select the types of non-woven fabric and air filter substrate having air permeability that is the same as or different from that of Example 16 shown in Table 9, and immerse the substrate composed of the selected non-woven fabric in the diluted solution of each water-repellent and oil-repellent film-forming liquid composition prepared in Examples 17 to 24 and Comparative Examples 10 to 18, deliquored and dried in the same manner as Example 1 to obtain an air filter having the characteristics shown in Table 9.

[0327] In addition, the nonwoven fabrics used in Example 23 and Comparative Example 17 are different from the nonwoven fabrics in Example 16 and are composed of a double layer of a nonwoven fabric of glass fiber and a nonwoven fabric of PET fiber. The air permeability of the air filters obtained by using the nonwoven fabrics used in Example 23 and Comparative Example 17 is 1.8 ml / cm 2 / sec and 0.1ml / cm 2 / Second.

[0328] <Comparative Test 3 and Evaluation>

[0329] The same simulated fluid as in Comparative Test 1 was used to simulate the oil mist and dust flying from a machine tool for machining metal products using a cutting fluid. The oil repellency of the water- and oil-repellent film (hereinafter referred to as the film) on the fiber surface of the nonwoven fabric constituting the air filter before and after the strength test was investigated for 18 air filters obtained in Examples 16 to 24 and Comparative Examples 10 to 18 using the simulated fluid.

[0330] (1) Oil repellency test before film strength test

[0331] Before the strength test of the film on the fiber surface of the nonwoven fabric constituting 18 kinds of horizontally placed air filters was performed, 1 ml of the obtained simulated liquid was dripped onto the air filter from above, and then the air filter was vertically erected to confirm the falling property of the simulated liquid. The situation where the simulated liquid infiltrated the air filter was set as "poor" oil repellency of the air filter, the situation where the simulated liquid did not infiltrate the air filter but adhered to its surface and if the air filter was vibrated, the situation where the simulated liquid fell from its surface was set as "slightly good" oil repellency of the air filter, and the situation where the simulated liquid fell from the air filter was set as "good" oil repellency of the air filter.

[0332] (2) Oil repellency test after film strength test

[0333] On 18 kinds of films evaluated, when following contact is applied with specified load, it is made to move back and forth 10 times under the following conditions.Then, confirm the falling property of simulation liquid in the same way as above-mentioned oil repellency test.The situation that simulation liquid is infiltrated into air filter is regarded as film peeling off because of the reciprocating motion of contact, and is made as oil repellency "bad".In addition, simulation liquid is not infiltrated into air filter and is attached to its surface and if air filter is vibrated, the situation that simulation liquid falls from its surface is regarded as not causing film peeling off because of the reciprocating motion of contact, and is made as oil repellency "slightly good", and the situation that simulation liquid falls from air filter immediately is made as not causing film peeling off because of the reciprocating motion of contact, and is made as oil repellency "good".

[0334] (a) Measuring instrument: Static and dynamic friction measuring machine TL201Tt (TrinityLab Co., Ltd.)

[0335] (b) Measurement conditions:

[0336] Moving distance: 30mm

[0337] Vertical load: 500g

[0338] ·Moving speed: 50mm / sec

[0339] Contact: 50mm×50mm square neoprene

[0340] As shown in Table 9, in the air filter of Comparative Example 10, the water-repellent and oil-repellent film-forming liquid composition is prepared by the comparative synthesis example 1 comprising the oxide (titanium dioxide) particles having an average particle diameter of 230nm. The air filter of Comparative Example 10 is made by impregnating nonwoven fabrics in the liquid composition and deliquating and drying, so the average particle diameter of oxide particles is too large, and it is difficult to bond oxide particles to the fiber surface of nonwoven fabrics by the silica sol gel as a binder component. As a result, before and after the strength test of film, simulated liquid will not fall from the air filter, and the oil repellency of the air filter before and after the strength test of film is "bad".

[0341] About the air filter of comparative example 11, since the oxide particles contain fluorine compounds, in the air filter before the strength test of the film, oil repellency is "good". However, after the strength test of the film, the water-repellent and oil-repellent film-forming liquid composition is prepared by the silica sol gel liquid of comparative synthesis example 6 without fluorine compounds, and the air filter is made of the liquid composition, so the simulated liquid infiltrates the air filter without falling, and the oil repellency is "bad". This can be considered that since fluorine compounds are not included in the silica sol gel, fluorine-containing oxide particles are easily gathered on the fiber surface of the non-woven fabric, and the film becomes a state of easy peeling by the strength test of the film.

[0342] In the air filter of comparative example 12, when the total amount of silica sol gel C and oxide particles B is set to 100 mass %, the containing ratio of silica sol gel C is too low and is 5 mass %, so the adhesive component in the liquid composition is too few. The air filter of comparative example 12 is made of the liquid composition, so the adhesive component for fixing oxide particles is less, and the simulated liquid easily penetrates between particles. Therefore, before and after the strength test of film, the simulated liquid will not fall from the air filter, and the oil repellency of the air filter before and after the strength test of film is "bad".

[0343] In the air filter of Comparative Example 13, when the total amount of silica sol gel C and oxide particles B is set to 100 mass %, the content ratio of silica sol gel C is 95 mass %, so the oil repellency before the strength test of the film is "slightly better". However, since the content ratio of oxide particles B is too low and is 5 mass %, the oxide particles in the liquid composition are too few, and in the strength test of the film, the film is peeled off from the fiber surface. Therefore, the oil repellency after the strength test of the film is "bad".

[0344] In the air filter of Comparative Example 14, the total content ratio (A1+A2) of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 is too low and is 0.8% by mass. The air filter of Comparative Example 14 is made of the liquid composition, so it is impossible to impart oil repellency to the formed film, and before and after the strength test of the film, the simulated liquid does not fall from the air filter, and the oil repellency of the air filter before and after the strength test of the film is "poor".

[0345] In the air filter of Comparative Example 15, the total containing ratio (A1+A2) of the first fluorinated functional group component A1 and the second fluorinated functional group component A2 is too high and is 35.2% by mass. The air filter of Comparative Example 15 is made of the liquid composition, so before the strength test of the film, its oil repellency is "good". However, due to too much fluorine-based compounds, uniform film cannot be formed, but becomes a porous state, and after the strength test of the film, the peeling of the film is produced, and its oil repellency is "bad".

[0346] Regarding the air filter of Comparative Example 16, a liquid composition for forming a water- and oil-repellent film is prepared by a dispersion of oxide particles of Comparative Synthesis Example 5 that does not contain fluorine-based compounds, and a film is formed from the liquid composition. Therefore, before and after the strength test of the membrane, the simulated liquid will not fall from the air filter, and the oil repellency of the air filter before and after the strength test of the membrane is "poor".

[0347] Regarding the air filter of Comparative Example 17, except that the air permeability of the air filter is 0.1 ml / cm 2 / s is too low, the diluent of the water-repellent and oil-repellent film-forming liquid composition will not fully penetrate into the nonwoven fabric, and the fiber surface of the nonwoven fabric will not fully form a water-repellent and oil-repellent film. Therefore, before the strength test of the film, the oil repellency is "good", but after the strength test of the film, the simulated liquid will not fall from the air filter, and the oil repellency of the air filter is "bad".

[0348] Regarding the air filter of Comparative Example 18, since the air permeability of the air filter is 32.2 ml / cm 2 / s is too high, so although a water-repellent and oil-repellent film is fully formed on the fiber surface of the nonwoven fabric, the simulated liquid penetrates into the nonwoven fabric due to the excessive pores. Therefore, before and after the strength test of the membrane, the simulated liquid does not fall from the air filter, and the oil repellency of the air filter before and after the strength test of the membrane is "poor".

[0349] In contrast, in the air filters of Examples 16 to 24, it can be confirmed that the oil repellency before the strength test of the membrane is all "good", and the water repellency after the friction test of the membrane using chloroprene rubber is all "good" or "slightly good". In particular, in Examples 16, 17 and 18, in which the content ratio of the first fluorine-containing functional group component A1 is greater than the content ratio of the second fluorine-containing functional group component A2 in terms of mass ratio and the fluorine-containing silica sol-gel liquid contains an alkylene component, the membrane strength test is also all "good".

[0350] Industrial Applicability

[0351] The air filter of the present invention is used in a working environment having a machine tool such as a cutting machine or a turning machine that processes metal products using a cutting fluid.

Claims

1. An air filter comprising a nonwoven fabric having a plurality of pores formed between fibers, wherein the plurality of pores extend between a surface through which air containing oil mist and dust flows in and another surface opposite to the surface through which the air flows out, A water- and oil-repellent film is formed on the fiber surface of the nonwoven fabric. The water- and oil-repellent film comprises a fluorine-containing functional group component A and a silica sol gel C. The fluorine-containing functional group component A is contained in an amount of 0.01% to 10% by mass when the silica sol gel C is 100% by mass, or in an amount of 1% to 30% by mass when the water- and oil-repellent film is 100% by mass, The air permeability of the air filter is 1ml / cm 2 / sec~30ml / cm 2 / Second, The fluorine-containing functional group component A comprises a perfluoroether structure represented by the following formula (1) or formula (2): C p F 2p+1 -O-C q F 2q -O-C r F 2r -X-Y (1) C p F 2p+1 -O-C q F 2q -X-Y (2) In the above formula (1) and the above formula (2), p, q and r are each the same or different integers of 1 to 6, the perfluoroether structure is linear or branched, and in addition, in the above formula (1) and the above formula (2), X is a hydrocarbon group having 2 to 10 carbon atoms, containing one or more bonds selected from ether bonds, CO-NH bonds, O-CO-NH bonds and sulfonamide bonds, and in the above formula (1) and the above formula (2), Y is a hydrolyzate of silane or a main component of a silica sol-gel.

2. The air filter according to claim 1, in, The water- and oil-repellent film comprises oxide particles B with an average particle size of 2 nm to 90 nm bonded to the fluorine-containing functional group component A and silica sol gel C. The fluorine-containing functional group component A and the oxide particles B are contained in a total amount of 5% to 80% by mass when the water- and oil-repellent film is taken as 100% by mass. The mass ratio A / B of the fluorine-containing functional group component A to the oxide particles B is in the range of 0.05 to 0.80, The oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

3. The air filter according to claim 1, in, The fluorine-containing functional group component A comprises a first fluorine-containing functional group component A1 bonded to oxide particles B having an average particle size of 2 nm to 90 nm and a second fluorine-containing functional group component A2 contained in the silica sol-gel C. When the water- and oil-repellent film is taken as 100 mass %, the total content ratio of the first fluorine-containing functional group component A1 and the second fluorine-containing functional group component A2 is 1 mass % to 30 mass %, The mass ratio C:B of the silica sol gel C and the oxide particles B is in the range of 10:90 to 90:

10. The oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

4. The air filter according to claim 3, in, The content ratio of the first fluorine-containing functional group component A1 is equal to or greater than the content ratio of the second fluorine-containing functional group component A2 in terms of mass ratio.

5. The air filter according to claim 1, in, The silica sol gel C contains 0.5 to 20% by mass of an alkylene component having 2 to 7 carbon atoms, based on 100% by mass of the silica sol gel C.

6. The air filter according to claim 1, in, The nonwoven fabric is composed of a single layer or a laminate of multiple layers.

7. The air filter according to claim 1, in, The fibers constituting the nonwoven fabric are one or more fibers selected from polyethylene terephthalate (PET), polypropylene (PP), glass, alumina, carbon, cellulose, pulp, nylon and metal.

8. A method for manufacturing an air filter as claimed in claim 1, comprising the following steps: A catalyst is added to a mixed solution of silicon alkoxide, a fluorine compound containing a fluorine-containing functional group component A, alcohol and water to prepare a liquid composition for forming a water- and oil-repellent film; mixing the water- and oil-repellent film-forming liquid composition and a solvent to prepare a dilution liquid; impregnating a nonwoven fabric in the diluent; as well as The impregnated nonwoven fabric is deliquified and dried, thereby forming a water- and oil-repellent film on the fiber surface of the nonwoven fabric.

9. A method for manufacturing an air filter as claimed in claim 2, comprising the following steps: dispersing oxide particles B in an organic solvent to prepare a dispersion of oxide particles; Mixing a fluorine compound containing a fluorine-containing functional group component A, water, and a catalyst into the dispersion of the oxide particles to prepare a dispersion of fluorine-containing oxide particles; A silica sol gel solution is prepared by adding a catalyst to a mixture of silicon alkoxide, alcohol and water; Mixing the dispersion of the fluorine-containing oxide particles and the diluted silica sol-gel solution to prepare a liquid composition for forming a water- and oil-repellent film; immersing a nonwoven fabric in a diluted solution of the water- and oil-repellent film-forming liquid composition; and The impregnated nonwoven fabric is dehydrated and dried, The oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

10. A method for manufacturing an air filter as claimed in claim 3, comprising the following steps: dispersing oxide particles B in an organic solvent to prepare a dispersion of oxide particles; Mixing a fluorine-containing compound containing a first fluorine-containing functional group component A1, water, and a catalyst into the dispersion of the oxide particles to prepare a dispersion of fluorine-containing oxide particles; A catalyst is added and mixed into a mixed solution of a fluorine-containing compound including a second fluorine-containing functional group component A2, a silicon alkoxide, an alcohol and water to prepare a fluorine-containing silica sol-gel solution; mixing the dispersion of the fluorine-containing oxide particles and the fluorine-containing silica sol-gel solution to prepare a liquid composition for forming a water- and oil-repellent film; immersing a nonwoven fabric in a diluted solution of the water- and oil-repellent film-forming liquid composition; and The impregnated nonwoven fabric is dehydrated and dried, The oxide particles B are oxide particles of one or two elements selected from Si, Al, Mg, Ca, Ti, Zn and Zr.

Citation Information

Patent Citations

  • Air filter medium, air filter pack, and air filter unit

    JP2018051546A

  • Surface treatment agent and method for producing the same, filter, and surface treatment method

    JP2018141063A